Crosslinked surface coatings and interfacial layers for perovskite material photovoltaic devices
Patent Information
- Application Number
- CN202080094358.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-11-27
- Filing Date
- 2020-11-23
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2040-11-23
Smart Images

Figure CN115023819B_ABST
Abstract
Description
[0001] Cross-reference to related applications
[0002] This application claims priority to U.S. Provisional Patent Application No. 62 / 941,320, filed November 27, 2019, entitled “CROSS LINKED SURFACE COATING AND INTERFACIAL LAYER FOR A PEROVSKITE MATERIAL PHOTOVOLTAIC DEVICE,” the entire contents of which are incorporated herein by reference. Background Technology
[0003] Using photovoltaics (PV) to generate electricity from solar energy or radiation offers numerous benefits, including, for example, power supply, low or zero emissions, grid-independent power generation, durable physical structure (no moving parts), stable and reliable systems, modular structure, relatively quick installation, safe manufacturing and use, and positive public opinion and acceptance.
[0004] Photovoltaics (PVs) can incorporate a perovskite material layer as a photoactive layer, generating electrical power when exposed to light. Additional layers in PV devices can facilitate charge transport from the photoactive layer. The choice of charge transport layer can influence the performance and durability of the PV device.
[0005] The features and advantages of this disclosure will be readily apparent to those skilled in the art. Although many modifications may be made by those skilled in the art, these modifications remain within the spirit of the invention. Summary of the Invention
[0006] According to some implementation schemes, a method for preparing perovskite photovoltaic devices includes: depositing perovskite material, depositing a fullerene layer, depositing a halosilylalkane, and heating an alkylhydroxide to combine the halosilylalkane with the fullerene.
[0007] According to some embodiments, the crosslinked polymer includes a halosilyl alkane and one or more monomers selected from the group consisting of polystyrene, methyl [6,6]-phenyl-C61-butyrate, poly(4-vinylphenol), [6,6]-phenyl-C61-butyric acid, and combinations thereof.
[0008] According to some embodiments, the photovoltaic device includes a photoactive material comprising a perovskite material. The photovoltaic device also includes an interface layer containing a crosslinked polymer comprising a halosilyl alkane and one or more monomers selected from: polystyrene, methyl [6,6]-phenyl-C61-butyrate, poly(4-vinylphenol), [6,6]-phenyl-C61-butyric acid, and combinations thereof. Attached Figure Description
[0009] Figure 1 This is a schematic diagram of a typical photovoltaic (PV) cell including an active layer, according to some embodiments of this disclosure.
[0010] Figure 2 This is a stylized diagram illustrating components of an example PV device according to some embodiments of the present disclosure.
[0011] Figure 3 This is a stylized diagram illustrating components of an example device according to some embodiments of the present disclosure.
[0012] Figure 4 This is a stylized diagram illustrating components of an example device according to some embodiments of the present disclosure.
[0013] Figure 5 This is a stylized diagram illustrating the Ruddlesden-Popper perovskite.
[0014] Figure 6 This is a stylized diagram illustrating a perovskite material with added alkylammonium cations according to some embodiments of the present disclosure.
[0015] Figure 7 This is a stylized diagram illustrating a perovskite material having a 1-butylammonium surface layer according to some embodiments of the present disclosure.
[0016] Figure 8 This is a stylized diagram illustrating a perovskite material having a surface layer of multiple giant organic cations according to some embodiments of the present disclosure.
[0017] Figure 8A This is a stylized diagram illustrating a perovskite material having a surface layer of multiple giant organic cations according to some embodiments of the present disclosure.
[0018] Figure 9 This is an illustration comparing images of perovskite materials with and without a 1-butylammonium (“BAI”) surface coating, according to some embodiments of this disclosure.
[0019] Figure 10This is a stylized diagram illustrating a comparison of images taken of perovskite materials with and without a 1-butylammonium (“BAI”) surface coating according to some embodiments of the present disclosure.
[0020] Figure 11A -D illustrates various perylene monoimides and diimides that can be applied to the surface of perovskite materials according to some embodiments of this disclosure.
[0021] Figure 12 This is a stylized diagram illustrating a perovskite material with added perylene monoimide ammonium cations according to some embodiments of the present disclosure.
[0022] Figure 13 This is a stylized diagram illustrating 1,4-diammonium butane incorporated into the lattice of a formamidinium lead iodide perovskite material according to some embodiments of the present disclosure.
[0023] Figure 14 This is a diagram of X-ray diffraction (XRD) peaks of perovskites with various concentrations of 1,4-diammonium butane according to some embodiments of this disclosure.
[0024] Figure 15 Images of perovskite material samples with various concentrations of 1,4-diammonium butane as a function of some embodiments of this disclosure are provided over time.
[0025] Figure 16 Illustrations of polyammonium alkyl cations according to some embodiments of the present disclosure are provided.
[0026] Figure 16A This is a stylized diagram illustrating 1,8-diammonium octane incorporated into the lattice of a formamidinium lead iodide perovskite material according to some embodiments of the present disclosure.
[0027] Figure 16B This is a stylized diagram illustrating bis(4-aminobutyl)-ammonium incorporated into the lattice of a formamidinium lead iodide perovskite material according to some embodiments of the present disclosure.
[0028] Figure 16C This is a stylized diagram illustrating tri(4-aminobutyl)-ammonium incorporated into the lattice of a formamidinium lead iodide perovskite material according to some embodiments of the present disclosure.
[0029] Figure 17-28 Illustrations of the structures of certain organic molecules according to some embodiments of this disclosure are provided.
[0030] Figure 29 X-ray diffraction patterns of perovskite materials according to some embodiments of the present disclosure are shown.
[0031] Figure 30 A stylized diagram of the thickness of the inorganic metal halide sublattice of a perovskite material according to some embodiments of the present disclosure is provided.
[0032] Figure 31 Optical and photoluminescence images of perovskite photovoltaic devices according to some embodiments of the present disclosure are shown.
[0033] Figure 32 Power output curves of perovskite photovoltaic devices according to some embodiments of the present disclosure are shown.
[0034] Figure 33 The current-voltage (IV) scans of perovskite photovoltaic devices according to some embodiments of the present disclosure are shown.
[0035] Figure 34 Box plots are shown of the open-circuit voltage (Voc), short-circuit current density (Jsc), fill factor (FF), and power conversion efficiency (PCE) of perovskite photovoltaic devices according to some embodiments of the present disclosure.
[0036] Figure 35 External quantum efficiency (EQE) curves of perovskite photovoltaic devices according to some embodiments of the present disclosure are shown.
[0037] Figure 36 Admittance spectra of perovskite photovoltaic devices according to some embodiments of the present disclosure are shown.
[0038] Figure 37 The structure of a cross-linked interface layer according to certain embodiments is shown.
[0039] Figure 38 The structure of a cross-linked interface layer according to certain embodiments is shown.
[0040] Figure 39 The structure of a cross-linked interface layer according to certain embodiments is shown.
[0041] Figure 40 The structure of a cross-linked interface layer according to certain embodiments is shown.
[0042] Figure 41 The structure of a cross-linked interface layer according to certain embodiments is shown.
[0043] Figure 42 The structure of a cross-linked interface layer according to certain embodiments is shown.
[0044] Figure 43 The structure of a cross-linked interface layer according to certain embodiments is shown.
[0045] Figure 44The structure of a cross-linked interface layer according to certain embodiments is shown.
[0046] Figure 45 The structure of a cross-linked interface layer according to certain embodiments is shown. Detailed Implementation
[0047] Improvements in various aspects of PV technologies compatible with organic, inorganic, and / or hybrid PV technologies promise to further reduce the cost of organic and other PV technologies. For example, some solar cells (such as perovskite PV solar cells) can utilize novel, cost-effective, and highly stable alternative components, such as nickel oxide interface layers. Furthermore, various solar cells can advantageously incorporate chemical additives and other materials that, among other advantages, may be more cost-effective and durable than currently available conventional options.
[0048] This disclosure generally relates to material compositions, apparatus, and methods for generating electrical energy from solar radiation using materials in photovoltaic cells. More specifically, this disclosure relates to photoactive and other material compositions, and apparatus and methods for using and forming such material compositions.
[0049] Some or all of the materials according to some embodiments of this disclosure may also be advantageously used in any organic or other electronic device, some examples including but not limited to: batteries, field-effect transistors (FETs), light-emitting diodes (LEDs), nonlinear optical devices, memristors, capacitors, rectifiers and / or rectifier antennas.
[0050] In some embodiments, this disclosure provides PV and other similar devices (e.g., batteries, hybrid PV batteries, multi-junction PV, FETs, LEDs, x-ray detectors, gamma-ray detectors, photodiodes, CCDs, etc.). In some embodiments, such devices may include improved active materials, interfacial layers (IFLs), and / or one or more perovskite materials. Perovskite materials may be incorporated into various aspects of one or more aspects of the PV or other devices. According to some embodiments, the perovskite material may have the general formula CMX3, wherein: C contains one or more cations (e.g., amines, ammonium, phosphonium, Group 1 metals, Group 2 metals, and / or other cations or cation-like compounds); M contains one or more metals (examples include Be, Mg, Ca, Sr, Ba, Fe, Cd, Co, Ni, Cu, Ag, Au, Hg, Sn, Ge, Ga, Pb, In, Tl, Sb, Bi, Ti, Zn, Cd, Hg, and Zr); and X contains one or more anions. Perovskite materials according to various embodiments will be discussed in more detail below.
[0051] Photovoltaic cells and other electronic devices
[0052] For reference Figure 1The illustrated solar cell depicts several PV embodiments. Example PV structures according to some embodiments may substantially have the form of substrate-anode-IFL-active layer-IFL-cathode. In some embodiments, the active layer may be photoactive, and / or may include photoactive materials. Other layers and materials may be used in the cell, as is known in the art. Furthermore, it should be noted that the use of the term "active layer" in no way implies limitation or otherwise express or implicitly restricts the nature of any other layer—for example, in some embodiments, one or both IFLs may also be active, as they may be semiconductor. Specifically, refer to… Figure 1 This paper depicts a stylized general-purpose PV cell 1000, illustrating the high interfacial properties of some layers within the PV. PV 1000 represents a general structure applicable to several PV devices, such as perovskite material PV implementations. The PV cell 1000 includes a transparent substrate layer 1010, which may be a glass (or a similarly transparent material to solar radiation) that allows solar radiation to pass through the layer. In some embodiments, the transparent layer may also be referred to as a top liner or substrate (e.g., as in...). Figure 2 The substrate layer 3901 may comprise any one or more of a variety of rigid or flexible materials, such as glass, polyethylene, polypropylene, polycarbonate, polyimide, PMMA, PET, PEN, Kapton, or quartz. Typically, the term substrate is used to refer to the material deposited thereon during device fabrication. The photoactive layer 1040 may be composed of: an electron donor or p-type material, and / or an electron acceptor or n-type material, and / or a bipolar semiconductor exhibiting both p-type and n-type material characteristics, and / or an intrinsic semiconductor exhibiting neither n-type nor p-type characteristics. In some embodiments, the photoactive layer 1040 may be a perovskite material as described herein. The active layer or photoactive layer 1040 (e.g., Figure 1 (As depicted) sandwiched between two conductive electrode layers 1020 and 1060. Figure 1 In this embodiment, electrode layer 1020 can be a transparent conductor, such as tin-doped indium oxide (ITO material) or other materials described herein. In other embodiments, the second substrate 1070 and the second electrode 1060 can be transparent. As previously mentioned, the active layer in some embodiments is not necessarily photoactive, although... Figure 1 The device shown is photoactive. The electrode layer 1060 can be aluminum or other metals, or other conductive materials, such as carbon. Other materials known in the art can be used. The battery 1010 also includes an interface layer (IFL) 1030, such as… Figure 1As shown in the example. IFL can facilitate charge separation. In other embodiments, IFL 1030 may include multilayer IFLs, which will be discussed in more detail below. IFL 1050 may also be present adjacent to electrode 1060. In some embodiments, IFL 1050 adjacent to electrode 1060 may also include or alternatively include multilayer IFLs (again, discussed in more detail below). IFLs according to some embodiments may be semiconductor in nature and may be intrinsic, bipolar, p-type or n-type, or they may be dielectric in nature. In some embodiments, IFLs on the cathode side of the device (e.g., as shown in the example) Figure 1 The IFL 1050 shown can be p-type, with the IFL on the anode side of the device (e.g., as shown in the image). Figure 1 The IFL 1030 shown can be n-type. However, in other embodiments, the cathode-side IFL can be n-type and the anode-side IFL can be p-type. The battery 1010 can be connected to electrical leads via electrodes 1060 and 1020 and a discharge unit, which can be such as a battery, motor, capacitor, power grid, or any other electrical load.
[0053] The various embodiments disclosed herein provide improved materials and / or designs in various aspects of solar cells and other devices, particularly including active materials (including hole transport layers and / or electron transport layers), interface layers, and overall device design.
[0054] Interface layer
[0055] In some embodiments, this disclosure provides advantageous materials and designs for one or more interface layers within a PV, including thin-coated IFLs. Thin-coated IFLs can be used in one or more IFLs of a PV according to the various embodiments discussed herein.
[0056] According to various embodiments, the device may optionally include an interface layer between any two other layers and / or materials; however, the device does not necessarily need to contain any interface layer. For example, perovskite material devices may contain zero, one, two, three, four, five, or more interface layers (e.g., Figure 2Example devices include five interface layers (3903, 3905, 3907, 3909, and 3911). The interface layers may include any suitable material for enhancing charge transport and / or collection between two layers or materials; it may also help prevent or reduce the likelihood of charge recombination once charge has been transported away from one of the materials adjacent to the interface layer. The interface layers may also physically and electrically homogenize its substrate, thereby inducing variations in substrate roughness, dielectric constant, adhesion, and the generation or quenching of defects (e.g., charge trapping, surface states). Suitable interface materials may include any one or more of the following: Ag; Al; Au; B; Bi; Ca; Cd; Ce; Co; Cu; Fe; Ga; Ge; H; In; Mg; Mn; Mo; Nb; Ni; Pt; Sb; Sc; Si; Sn; Ta; Ti; V; W; Y; Zn; Zr; carbides of any of the above metals (e.g., SiC, Fe3C, WC, VC, MoC, NbC); silicides of any of the above metals (e.g., Mg2Si, SrS). i2, Sn2Si); oxides of any of the above metals (e.g., aluminum oxide, silicon oxide, titanium oxide, SnO2, ZnO, NiO, ZrO2, HfO2), including transparent conductive oxides (“TCO”), such as indium tin oxide, aluminum-doped zinc oxide (AZO), cadmium oxide (CdO) and fluorine-doped tin oxide (FTO); sulfides of any of the above metals (e.g., CdS, MoS2, SnS2); nitrides of any of the above metals (e.g., GaN, Mg3N2, TiN). BN, Si3N4); selenides of any of the above metals (e.g., CdSe, FeSe2, ZnSe); tellurides of any of the above metals (e.g., CdTe, TiTe2, ZnTe); phosphides of any of the above metals (e.g., InP, GaP, GaInP); arsenides of any of the above metals (e.g., CoAs3, GaAs, InGaAs, NiAs); antimonides of any of the above metals (e.g., AlSb, GaSb, InSb); any of the above metals Halides of the metals mentioned above (e.g., CuCl, CuI, BiI3); pseudohalides of any of the aforementioned metals (e.g., CuSCN, AuCN, Fe(SCN)2); carbonates of any of the aforementioned metals (e.g., CaCO3, Ce2(CO3)3); functionalized or non-functionalized alkylsilyl groups; graphite; graphene; fullerene; carbon nanotubes; any mesoporous materials and / or interface materials discussed elsewhere herein; and combinations thereof (in some embodiments, including bilayer, trilayer, or multilayer combinations). In some embodiments, the interface layer may comprise a perovskite material. Furthermore, the interface layer may comprise any doped embodiment of the interface material mentioned herein (e.g., Y-doped ZnO, N-doped single-walled carbon nanotubes).The interface layer may also contain compounds having three of the above-mentioned materials (e.g., CuTiO3, Zn2SnO4) or compounds having four of the above-mentioned materials (e.g., CoNiZnO). The materials listed above may exist in planar, mesoporous or other nanostructure forms (e.g., rods, spheres, flowers, pyramids) or aerogel structures.
[0057] First, as mentioned earlier, one or more IFLs (e.g., Figure 1 One or both of IFLs 2626 and 2627 shown may contain the photoactive organic compound of this disclosure as a self-assembled monolayer (SAM) or as a thin film. When the photoactive organic compound of this disclosure is used as a SAM, it may contain a binding group through which it may be covalently or otherwise bound to the surface of one or both of the anode and cathode. The binding group in some embodiments may include any one or more of the following: COOH, SiX3 (where X may be any moiety suitable for forming a ternary silicon compound, such as Si(OR)3 and SiCl3), SO3, PO4H, OH, CH2X (where X may include a Group 17 halide ion), and O. The binding group may be covalently or otherwise bound to an electron-withdrawing moiety, an electron-donating moiety, and / or a core moiety. The binding group may be attached to the electrode surface in a manner that forms a monomolecular (or multiple molecules in some embodiments) thick, oriented ordered layer (i.e., where multiple photoactive organic compounds are bound to the anode and / or cathode). As described above, SAMs can be linked via covalent interactions, but in some embodiments, they can be linked via ionic, hydrogen bond, and / or dispersive forces (i.e., van der Waals forces). Furthermore, in some embodiments, upon exposure, the SAM can enter a zwitterionic excited state, thereby generating a highly polarized IFL that can guide charge carriers from the active layer to the electrode (e.g., anode or cathode). In some embodiments, this enhanced charge carrier injection can be achieved by electronically polarizing the cross-section of the active layer and thus increasing the charge carrier drift velocity toward their respective electrodes (e.g., holes to anode; electrons to cathode). Molecules for anode applications in some embodiments may comprise tunable compounds comprising a primary electron donor structural portion bound to a core structural portion, which in turn is bound to an electron-withdrawing structural portion, which in turn is bound to a binding group. In cathode applications according to some embodiments, IFL molecules may comprise tunable compounds comprising an electron-deficient structural portion bound to a core structural portion, which in turn is bound to an electron donor structural portion, which in turn is bound to a binding group. When a photoactive organic compound is used as an IFL according to these embodiments, it can retain its photoactive properties; however, in some embodiments it does not need to be photoactive.
[0058] Metal oxides can be used in the thin-film IFL of some embodiments and can include semiconductor metal oxides such as NiO, SnO2, WO3, V2O5, or MoO3. Embodiments in which the second (e.g., n-type) active material comprises a TiO2 coated with a thin-film IFL containing Al2O3 can be formed, for example, using a precursor material such as Al(NO3)3·xH2O or any other material suitable for depositing Al2O3 onto TiO2, followed by thermal annealing and dye coating. In exemplary embodiments where a MoO3 coating is used as an alternative, the coating can be formed with a precursor material such as Na2MO4·2H2O; while a V2O5 coating according to some embodiments can be formed with a precursor material such as NaVO3; and a WO3 coating according to some embodiments can be formed with a precursor material such as NaWO4·H2O. The concentration of the precursor material (e.g., Al(NO3)3·xH2O) can affect the final film thickness (here, Al2O3) deposited on TiO2 or other active materials. Therefore, varying the concentration of the precursor material can be a method to control the final film thickness. For example, a higher precursor material concentration may result in a greater film thickness. In PV devices containing metal oxide coatings, a larger film thickness does not necessarily lead to a larger PCE. Therefore, some embodiments may include coating a TiO2 (or other mesoporous) layer with a precursor material concentration in the range of about 0.5 to 10.0 mM; other embodiments may include coating the layer with a precursor material concentration in the range of about 2.0 to 6.0 mM; or, in other embodiments, about 2.5 to 5.5 mM.
[0059] Furthermore, although referred to herein as Al2O3 and / or alumina, it should be noted that different ratios of aluminum and oxygen can be used in the formation of alumina. Therefore, while some embodiments discussed herein are described with respect to Al2O3, this description is not intended to limit the required ratio of aluminum to oxygen. Rather, embodiments may include any one or more alumina compounds, each having a specific ratio according to Al… x O y The alumina ratio, where x can be any value between about 1 and 100, an integer or a non-integer. In some embodiments, x can be between about 1 and 3 (and again, it does not have to be an integer). Similarly, y can be any value between 0.1 and 100, an integer or a non-integer. In some embodiments, y can be between 2 and 4 (and again, it does not have to be an integer). Furthermore, Al can be present in various embodiments. x O y Various crystalline forms, such as the α, γ and / or amorphous forms of aluminum oxide.
[0060] Similarly, although referred to herein as NiO, MoO3, WO3, and V2O5, these compounds may alternatively or otherwise be represented as Ni. x O y Mo x O y W x O y and V x O y Regarding Mo x O y and W x O y In each of these, x can be any value between approximately 0.5 and 100, an integer or a non-integer; in some implementations, it can be between approximately 0.5 and 1.5. Similarly, y can be any value between approximately 1 and 100, an integer or a non-integer. In some implementations, y can be any value between approximately 1 and 4. Regarding V... x O y x can be any value between about 0.5 and 100, an integer or a non-integer; in some embodiments, it can be between about 0.5 and 1.5. Similarly, y can be any value between about 1 and 100, an integer or a non-integer; in some embodiments, it can be an integer or a non-integer value between about 1 and 10. In some embodiments, the values of x and y can be in a non-stoichiometric ratio. It should be noted that any IFL material written as a stoichiometric ratio in this invention can also be present in a non-stoichiometric ratio as in the examples above.
[0061] In some embodiments, the IFL may comprise a titanate. According to some embodiments, the titanate may have the general formula M'TiO3, where M' comprises any 2+ cation. In some embodiments, M' may comprise the cation form of Be, Mg, Ca, Sr, Ba, Ni, Zn, Cd, Hg, Cu, Pd, Pt, Sn, or Pb. In some embodiments, the IFL may comprise a single type of titanate, while in other embodiments, the IFL may comprise two or more different types of titanates. In one embodiment, the titanate has the formula SrTiO3. In another embodiment, the titanate may have the formula BaTiO3. In yet another embodiment, the titanate may have the formula CaTiO3.
[0062] As an explanation, and without implying any limitations, titanates possess a perovskite crystal structure and strongly initiate the growth and transformation processes of perovskite materials such as lead methylammonium iodide (MAPbI3) and lead formamidinium iodide (FAPbI3). Titanates also typically satisfy other IFL requirements, such as ferroelectric behavior, sufficient charge carrier mobility, optical transparency, matched energy levels, and a high dielectric constant.
[0063] In other embodiments, the IFL may comprise a zirconate. According to some embodiments, the zirconate may have the general formula M'ZrO3, where M' comprises any 2+ cation. In some embodiments, M' may comprise the cation form of Be, Mg, Ca, Sr, Ba, Ni, Zn, Cd, Hg, Cu, Pd, Pt, Sn, or Pb. In some embodiments, the IFL may comprise a single type of zirconate, while in other embodiments, the IFL may comprise two or more different types of zirconates. In one embodiment, the zirconate has the formula SrZrO3. In another embodiment, the zirconate may have the formula BaZrO3. In yet another embodiment, the zirconate may have the formula CaZrO3.
[0064] As an explanation, and without implying any limitations, zirconates possess a perovskite crystal structure and strongly initiate the growth transformation process of perovskite materials (e.g., MAPbI3, FAPbI3). Zirconates also typically satisfy other IFL requirements, such as ferroelectric behavior, sufficient charge carrier mobility, optical transparency, matched energy levels, and a high dielectric constant.
[0065] In other embodiments, the IFL may comprise a stannate. According to some embodiments, the stannate may have the general formula M'SnO3 or M'2SnO4, wherein M' comprises any 2+ cation. In some embodiments, M' may comprise the cation form of Be, Mg, Ca, Sr, Ba, Ni, Zn, Cd, Hg, Cu, Pd, Pt, Sn, or Pb. In some embodiments, the IFL may comprise a single type of stannate, while in other embodiments, the IFL may comprise two or more different types of stannates. In one embodiment, the stannate has the formula SrSnO3. In another embodiment, the stannate may have the formula BaSnO3. In yet another embodiment, the stannate may have the formula CaSnO3.
[0066] As an explanation, and without implying any limitations, stannates possess a perovskite crystal structure and strongly initiate the growth transformation process of perovskite materials (e.g., MAPbI3, FAPbI3). Stannates also typically satisfy other IFL requirements, such as ferroelectric behavior, sufficient charge carrier mobility, optical transparency, matched energy levels, and high dielectric constant.
[0067] In other embodiments, the IFL may comprise a leadate. According to some embodiments, the leadate may have the general formula M'PbO3, where M' comprises any 2+ cation. In some embodiments, M' may comprise the cation form of Be, Mg, Ca, Sr, Ba, Ni, Zn, Cd, Hg, Cu, Pd, Pt, Sn, or Pb. In some embodiments, the IFL may comprise a single type of leadate, while in other embodiments, the IFL may comprise two or more different types of leadates. In one embodiment, the leadate has the formula SrPbO3. In another embodiment, the leadate may have the formula BaPbO3. In yet another embodiment, the leadate may have the formula CaPbO3. In yet another embodiment, the leadate may have the formula Pb II Pb IV O3.
[0068] As an explanation, and without implying any limitations, leadates possess a perovskite crystal structure and strongly initiate the growth transformation process of perovskite materials (e.g., MAPbI3, FAPbI3). Leadates also typically satisfy other IFL requirements, such as ferroelectric behavior, sufficient charge carrier mobility, optical transparency, matched energy levels, and high dielectric constant.
[0069] Furthermore, in other embodiments, the IFL may include the general formula M'[Zr x Ti 1-x The IFL is a combination of zirconate and titanate of O3, wherein X is greater than 0 but less than 1, and M' comprises any 2+ cation. In some embodiments, M' may comprise the cation form of Be, Mg, Ca, Sr, Ba, Ni, Zn, Cd, Hg, Cu, Pd, Pt, Sn, or Pb. In some embodiments, the IFL may comprise a single type of zirconate, while in other embodiments, the IFL may comprise two or more different types of zirconates. In one embodiment, the zirconate / titanium combination has the formula Pb[Zr x Ti 1-x O3. In another embodiment, the zirconate / titaniumate combination has the formula Pb[Zr 0.52 Ti 0.48 ]O3.
[0070] As an explanation, and without implying any limitations, the zirconate / titanium combination exhibits a perovskite crystal structure and strongly initiates the growth transformation process of perovskite materials (e.g., MAPbI3, FAPbI3). The zirconate / titanium combination also typically satisfies other IFL requirements, such as ferroelectric behavior, sufficient charge carrier mobility, optical transparency, matched energy levels, and a high dielectric constant.
[0071] In other embodiments, the IFL may comprise a niobate. According to some embodiments, the niobate may have the general formula M'NbO3, wherein M' comprises any 1+ cation. In some embodiments, M' may comprise the cation form of Li, Na, K, Rb, Cs, Cu, Ag, Au, Tl, ammonium, or H. In some embodiments, the IFL may comprise a single type of niobate, while in other embodiments, the IFL may comprise two or more different types of niobates. In one embodiment, the niobate has the formula LiNbO3. In another embodiment, the niobate may have the formula NaNbO3. In yet another embodiment, the niobate may have the formula AgNbO3.
[0072] As an explanation, and without implying any limitations, niobates generally meet IFL requirements, such as piezoelectric behavior, nonlinear optical polarizability, photoelasticity, ferroelectric behavior, Pockels effect, sufficient charge carrier mobility, optical transparency, matched energy levels, and high dielectric constant.
[0073] In one embodiment, perovskite devices can be fabricated by casting PbI2 onto a SrTiO3-coated ITO substrate. The PbI2 can be converted to MAPbI3 via an impregnation process. This process will be described in more detail below. Compared to substrate fabrication without SrTiO3, this final conversion from PbI2 to MAPbI3 may be more complete (as observed by spectroscopic methods).
[0074] Any interface material discussed herein may further include doped compositions. To modify the properties of the interface material (e.g., electrical, optical, mechanical), it can be doped with one or more elements (e.g., Na, Y, Mg, N, P) in stoichiometric or non-stoichiometric amounts ranging from 1 ppb to 50 mol%. Some examples of interface materials include: NiO, TiO2, SrTiO3, Al2O3, ZrO2, WO3, V2O5, MO3, ZnO, graphene, and carbon black. Examples of possible dopants for these interface materials include: Li, Na, Be, Mg, Ca, Sr, Ba, Sc, Y, Nb, Ti, Fe, Co, Ni, Cu, Ga, Sn, In, B, N, P, C, S, As, halides, pseudohalides (e.g., cyanides, cyanates, isocyanates, fulminates, thiocyanates, isothiocyanates, azides, tetracarbonylcobaltate, carbamoyl dicyanomethane, dicyanonitromethane, dicyanamide, and tricyanomethane) and Al in any oxidation state. The mention of doped interface materials herein is not intended to limit the ratio of component elements in the interface material compound.
[0075] In some implementations, multiple IFLs made of different materials can be arranged adjacent to each other to form a composite IFL. This configuration may involve two different IFLs, three different IFLs, or a larger number of different IFLs. The resulting multilayered or composite IFL can be used in place of a single-material IFL. For example, a composite IFL can be used... Figure 2 Any IFL shown in the examples, such as IFL 3903, IFL 3905, IFL 3907, IFL 3909, or IFL 3911. Although composite IFLs differ from single-material IFLs, the assembly of perovskite PV cells with multilayer IFLs is not substantially different from the assembly of perovskite PV cells with only single-material IFLs.
[0076] Generally, composite IFLs can be fabricated using any of the materials discussed herein that are suitable for IFLs. In one embodiment, the IFL comprises a layer of Al₂O₃ and a layer of ZnO or M:ZnO (doped ZnO, such as Be:ZnO, Mg:ZnO, Ca:ZnO, Sr:ZnO, Ba:ZnO, Sc:ZnO, Y:ZnO, Nb:ZnO). In another embodiment, the IFL comprises a layer of ZrO₂ and a layer of ZnO or M:ZnO. In some embodiments, the IFL comprises multiple layers. In some embodiments, multilayer IFLs typically have a conductor layer, a dielectric layer, and a semiconductor layer. In certain embodiments, these layers may be repeated, for example, a conductor layer, a dielectric layer, a semiconductor layer, and a dielectric layer and a semiconductor layer. Examples of multilayer IFLs include: IFLs having an ITO layer, an Al2O3 layer, a ZnO layer, and a second Al2O3 layer; IFLs having an ITO layer, an Al2O3 layer, a ZnO layer, a second Al2O3 layer, and a second ZnO layer; IFLs having an ITO layer, an Al2O3 layer, a ZnO layer, a second Al2O3 layer, a second ZnO layer, and a third Al2O3 layer; and IFLs with multiple layers necessary to achieve the desired performance characteristics. As previously stated, mentioning certain stoichiometric ratios is not intended to limit the ratio of constituent elements in the IFL layers according to various embodiments.
[0077] In perovskite PV cells, using two or more adjacent integrated electrode layers (IFLs) as a composite IFL may be superior to a single IFL, where the properties of each IFL material can be utilized within the single IFL. For example, in a structure with an ITO layer, an Al2O3 layer, and a ZnO layer, ITO is the conductive electrode, Al2O3 is the dielectric material, and ZnO is an n-type semiconductor, acting as an electron acceptor with excellent electron transport properties (e.g., mobility). Furthermore, Al2O3 is a physically robust material that can adhere well to ITO, homogenizing the surface by covering surface defects (e.g., charge traps) and improving the device's diode characteristics by suppressing dark current.
[0078] Furthermore, some perovskite PV cells can include so-called "tandem" PV cells with more than one perovskite photoactive layer. For example, Figure 2 The photoactive materials 3908 and 3906 can both be perovskite materials. In this type of series-connected PV cell, the interface layer between the two photoactive layers is, for example... Figure 2 The IFL 3907 (i.e., the composite layer) may include multiple or composite IFLs. In some embodiments, the layer sandwiched between two photoactive layers of the tandem PV device may include an electrode layer.
[0079] A cascaded PV device may include the following layers, listed in order from top to bottom or bottom to top: a first substrate, a first electrode, a first interface layer, a first perovskite material, a second interface layer, a second electrode, a third interface layer, a second perovskite material, a fourth interface layer, and a third electrode. In some embodiments, the first and third interface layers may be hole transport interface layers, and the second and fourth interface layers may be electron transport interface layers. In other embodiments, the first and third interface layers may be electron transport interface layers, and the second and fourth interface layers may be hole transport interface layers. In yet another embodiment, the first and fourth interface layers may be hole transport interface layers, and the second and third interface layers may be electron transport interface layers. In still another embodiment, the first and fourth interface layers may be electron transport interface layers, and the second and third interface layers may be hole transport interface layers. In a cascaded PV device, the first and second perovskite materials may have different band gaps. In some embodiments, the first perovskite material may be formamidinium lead bromide (FAPbBr3), and the second perovskite material may be formamidinium lead iodide (FAPbI3). In other embodiments, the first perovskite material may be lead methylammonium bromide (MAPbBr3), and the second perovskite material may be lead formamidinium iodide (FAPbI3).
[0080] Perovskite materials
[0081] Perovskite materials can be incorporated into one or more aspects of PVs or other devices. According to some embodiments, perovskite materials can have the general formula Ci. w M y X zThe formula is defined as follows: C comprises one or more cations (e.g., amines, ammonium, phosphonium, Group 1 metals, Group 2 metals, and / or other cations or cation-like compounds); M comprises one or more metals (examples include Be, Mg, Ca, Sr, Ba, Fe, Cd, Co, Ni, Cu, Ag, Au, Hg, Sn, Ge, Ga, Pb, In, Tl, Sb, Bi, Ti, Zn, Cd, Hg, and Zr); X comprises one or more anions; and w, y, and z represent real numbers from 1 to 20. In some embodiments, C may comprise one or more organic cations. In some embodiments, each organic cation C may be larger than each metal M, and each anion X may be able to bind to both cation C and metal M. In a particular embodiment, the perovskite material may have the formula CMX3.
[0082] In some implementations, C may include ammonium, i.e., the general formula [NR4]. + Organic cations, wherein the R groups can be the same or different groups. Suitable R groups include, but are not limited to: hydrogen, methyl, ethyl, propyl, butyl, pentyl or isomers thereof; any alkane, alkene or alkyne CxHy, wherein x = 1-20, y = 1-42, cyclic, branched or straight-chain; haloalkanes, CxHyXz, x = 1-20, y = 0-42, z = 1-42, X = F, Cl, Br or I; any aromatic group (e.g. phenyl, alkylphenyl, alkoxyphenyl, pyridine, naphthalene); cyclic complexes containing at least one nitrogen atom (e.g. pyridine, pyrrole, pyrrolidine, piperidine, tetrahydroquinoline); any Sulfur-containing groups (e.g., sulfoxides, thiols, alkyl sulfides); any nitrogen-containing group (nitrooxygen, amine); any phosphorus-containing group (phosphate); any boron-containing group (e.g., boric acid); any organic acid (e.g., acetic acid, propionic acid); and its esters or amide derivatives; any amino acid (e.g., glycine, cysteine, proline, glutamic acid, arginine, serine, histidine, 5-ammonium valerate), including α, β, γ and larger derivatives; any silicon-containing group (e.g., siloxanes); and any alkoxy or group -OCxHy, where x = 0-20 and y = 1-42.
[0083] In some implementations, C may include formamidinium, or the general formula [R2NCRNR2]. +Organic cations, wherein the R groups can be the same or different groups. Suitable R groups include, but are not limited to: hydrogen, methyl, ethyl, propyl, butyl, pentyl or isomers thereof; any alkane, alkene or alkyne CxHy, wherein x = 1-20, y = 1-42, cyclic, branched or straight-chain; haloalkanes, CxHyXz, x = 1-20, y = 0-42, z = 1-42, x = F, Cl, Br or I; any aromatic group (e.g. phenyl, alkylphenyl, alkoxyphenyl, pyridine, naphthalene); cyclic complexes containing at least one nitrogen atom (e.g. imidazole, benzimidazole, pyrimidine, (azolidinylidenemet)pyrrolidine). (hyl)pyrrolidine), triazole); any sulfur-containing group (e.g., sulfoxide, thiol, alkyl sulfide); any nitrogen-containing group (nitrooxy, amine); any phosphorus-containing group (phosphate); any boron-containing group (e.g., boric acid); any organic acid (acetic acid, propionic acid) and its ester or amide derivatives; any amino acid (e.g., glycine, cysteine, proline, glutamic acid, arginine, serine, histidine, 5-ammonium valerate), including α, β, γ and larger derivatives; any silicon-containing group (e.g., siloxane); and any alkoxy or group -OCxHy, where x = 0-20, y = 1-42.
[0084]
[0085] Equation 1 shows the general formula [R2NCRNR2] described above. + The structure of formamidinium cations. Formula 2 shows example structures of several formamidinium cations that can serve as cations "C" in perovskite materials.
[0086]
[0087]
[0088] In some implementations, C may include guanidine, i.e., the general formula [(R₂N)₂C = NR₂]. +Organic cations, wherein the R groups can be the same or different groups. Suitable R groups include, but are not limited to: hydrogen, methyl, ethyl, propyl, butyl, pentyl or isomers thereof; any alkane, alkene or alkyne CxHy, wherein x = 1-20, y = 1-42, cyclic, branched or straight-chain; haloalkanes, CxHyXz, x = 1-20, y = 0-42, z = 1-42, x = F, Cl, Br or I; any aromatic group (e.g. phenyl, alkylphenyl, alkoxyphenyl, pyridine, naphthalene); cyclic complexes containing at least one nitrogen atom (e.g., octahydropyrimidino[1,2-a]pyrimidine, pyrimidino[1,2-a]pyrimidine, hexahydroimidazo[1,2-a]pyrimidine). -a] imidazole, hexahydropyrimidine-2-imine); any sulfur-containing group (e.g., sulfoxide, thiol, alkyl sulfide); any nitrogen-containing group (nitrooxy, amine); any phosphorus-containing group (phosphate); any boron-containing group (e.g., boric acid); any organic acid (acetic acid, propionic acid) and its ester or amide derivatives; any amino acid (e.g., glycine, cysteine, proline, glutamic acid, arginine, serine, histidine, 5-ammonium valerate), including α, β, γ and larger derivatives; any silicon-containing group (e.g., siloxane); and any alkoxy or group -OCxHy, where x = 0-20, y = 1-42.
[0089]
[0090] Equation 3 shows the general formula [(R2N)2C=NR2] above. + The structure of guanidinium cations. Equation 4 shows several structural examples of guanidinium cations that can serve as cations "C" in perovskite materials.
[0091]
[0092]
[0093] In some embodiments, C may include an ethylenetetramine cation, i.e., the general formula [(R₂N)₂C=C(NR₂)₂] +Organic cations, wherein the R groups can be the same or different groups. Suitable R groups include, but are not limited to: hydrogen, methyl, ethyl, propyl, butyl, pentyl or isomers thereof; any alkane, alkene or alkyne CxHy, wherein x = 1-20, y = 1-42, cyclic, branched or straight-chain; haloalkanes, CxHyXz, x = 1-20, y = 0-42, z = 1-42, x = F, Cl, Br or I; any aromatic group (e.g. phenyl, alkylphenyl, alkoxyphenyl, pyridine, naphthalene); cyclic complexes containing at least one nitrogen atom (e.g. 2-hexahydropyrimidin-2-ylidenehexahydropyrimidin, octahydropyrazino[2,3-b]pyrazine, pyrazino[2,3-b... [Pyrazine, quinoxalo[2,3-b]quinoxalo]; any sulfur-containing group (e.g., sulfoxide, thiol, alkyl sulfide); any nitrogen-containing group (nitrooxy, amine); any phosphorus-containing group (phosphate); any boron-containing group (e.g., boric acid); any organic acid (acetic acid, propionic acid) and its ester or amide derivatives; any amino acid (e.g., glycine, cysteine, proline, glutamic acid, arginine, serine, histidine, 5-ammonium valerate), including α, β, γ and larger derivatives; any silicon-containing group (e.g., siloxane); and any alkoxy or group -OCxHy, where x = 0-20, y = 1-42.
[0094]
[0095] Equation 5 shows the general formula [(R2N)2C=C(NR2)2] above. + The structure of the ethylenetetramine cation. Formula 6 shows several structural examples of ethylenetetramine ions, which can serve as cations "C" in perovskite materials.
[0096]
[0097] In some embodiments, C may include an imidazolium cation, i.e., the general formula [CRNRCRNRCR] +Aromatic cyclic organic cations, wherein the R groups can be the same or different groups. Suitable R groups can include, but are not limited to: hydrogen, methyl, ethyl, propyl, butyl, pentyl or isomers thereof; any alkane, alkene or alkyne CxHy, wherein x = 1-20, y = 1-42, cyclic, branched or straight-chain; haloalkanes, CxHyXz, x = 1-20, y = 0-42, z = 1-42, X = F, Cl, Br or I; any aromatic group (e.g. phenyl, alkylphenyl, alkoxyphenyl, pyridine, naphthalene); cyclic complexes containing at least one nitrogen atom (e.g. 2-hexahydropyrimidin-2-ylidenehexahydropyrimidin, octahydropyrazino[2,3-b]pyrazine, pyrazino[2,3-b]pyrazine, etc. [b]pyrazine, quinoxalo[2,3-b]quinoxalo; any sulfur-containing group (e.g., sulfoxide, thiol, alkyl sulfide); any nitrogen-containing group (nitrooxy, amine); any phosphorus-containing group (phosphate); any boron-containing group (e.g., boric acid); any organic acid (acetic acid, propionic acid) and its ester or amide derivatives; any amino acid (e.g., glycine, cysteine, proline, glutamic acid, arginine, serine, histidine, 5-ammonium valerate), including α, β, γ and larger derivatives; any silicon-containing group (e.g., siloxane); and any alkoxy or group -OCxHy, where x = 0-20, y = 1-42.
[0098] In some embodiments, C may include a pyridium cation, i.e., the general formula [CRCRCRCRCRNR]. + Aromatic cyclic organic cations, wherein the R groups can be the same or different groups. Suitable R groups can include, but are not limited to: hydrogen, methyl, ethyl, propyl, butyl, pentyl or isomers thereof; any alkane, alkene or alkyne CxHy, wherein x = 1-20, y = 1-42, cyclic, branched or straight-chain; haloalkanes, CxHyXz, x = 1-20, y = 0-42, z = 1-42, X = F, Cl, Br or I; any aromatic group (e.g. phenyl, alkylphenyl, alkoxyphenyl, pyridine, naphthalene); cyclic complexes containing at least one nitrogen atom (e.g. 2-hexahydropyrimidin-2-ylidenehexahydropyrimidin, octahydropyrazino[2,3-b]pyrazine, pyrazino[2,3-b]pyrazine, etc. [b]pyrazine, quinoxalo[2,3-b]quinoxalo; any sulfur-containing group (e.g., sulfoxide, thiol, alkyl sulfide); any nitrogen-containing group (nitrooxy, amine); any phosphorus-containing group (phosphate); any boron-containing group (e.g., boric acid); any organic acid (acetic acid, propionic acid) and its ester or amide derivatives; any amino acid (e.g., glycine, cysteine, proline, glutamic acid, arginine, serine, histidine, 5-ammonium valerate), including α, β, γ and larger derivatives; any silicon-containing group (e.g., siloxane); and any alkoxy or group -OCxHy, where x = 0-20, y = 1-42.
[0099]
[0100] In some embodiments, X may include one or more halide ions. In some embodiments, X may alternatively or additionally include a Group 16 anion. In some embodiments, the Group 16 anion may be an oxide, sulfide, selenide, or telluride. In some embodiments, X may alternatively or additionally include one or more pseudohalides (e.g., cyanide, cyanate, isocyanate, fulminate, thiocyanate, isothiocyanate, azide, tetracarbonylcobaltate, carbamoyl dicyanomethane, dicyanonitromethane, dicyanamide, and tricyanomethane).
[0101] In one embodiment, the perovskite material may comprise the empirical formula CMX3, wherein: C comprises one or more of the above-described cations, Group 1 metals, Group 2 metals and / or other cations or cation-like compounds; M comprises one or more metals (examples include Be, Mg, Ca, Sr, Ba, Fe, Cd, Co, Ni, Cu, Ag, Au, Hg, Sn, Ge, Ga, Pb, In, Tl, Sb, Bi, Ti, Zn, Cd, Hg and Zr); and X comprises one or more of the above-described anions.
[0102] In another embodiment, the perovskite material may include the empirical formula C'M2X6, wherein: C' comprises a cation having a 2+ charge, including one or more of the above-described cations, diammonium butane, a Group 1 metal, a Group 2 metal, and / or other cations or cation-like compounds; M comprises one or more metals (examples include Be, Mg, Ca, Sr, Ba, Fe, Cd, Co, Ni, Cu, Ag, Au, Hg, Sn, Ge, Ga, Pb, In, Tl, Sb, Bi, Ti, Zn, Cd, Hg, and Zr); and X comprises one or more of the above-described anions.
[0103] In another embodiment, the perovskite material may include the empirical formula C'MX4, wherein: C' comprises a cation having a 2+ charge, including one or more of the above-described cations, diammonium butane, a Group 1 metal, a Group 2 metal, and / or other cations or cationic compounds; M comprises one or more metals (examples include Be, Mg, Ca, Sr, Ba, Fe, Cd, Co, Ni, Cu, Ag, Au, Hg, Sn, Ge, Ga, Pb, In, Tl, Sb, Bi, Ti, Zn, Cd, Hg, and Zr); and X comprises one or more of the above-described anions. In this embodiment, the perovskite material may have a 2D structure.
[0104] In one embodiment, the perovskite material may comprise the empirical formula C3M2X9, wherein: C comprises one or more of the above-described cations, Group 1 metals, Group 2 metals and / or other cations or cation-like compounds; M comprises one or more metals (examples include Be, Mg, Ca, Sr, Ba, Fe, Cd, Co, Ni, Cu, Ag, Au, Hg, Sn, Ge, Ga, Pb, In, Tl, Sb, Bi, Ti, Zn, Cd, Hg and Zr); and X comprises one or more of the above-described anions.
[0105] In one embodiment, the perovskite material may comprise the empirical formula CM2X7, wherein: C comprises one or more of the above-described cations, Group 1 metals, Group 2 metals and / or other cations or cation-like compounds; M comprises one or more metals (examples include Be, Mg, Ca, Sr, Ba, Fe, Cd, Co, Ni, Cu, Ag, Au, Hg, Sn, Ge, Ga, Pb, In, Tl, Sb, Bi, Ti, Zn, Cd, Hg and Zr); and X comprises one or more of the above-described anions.
[0106] In one embodiment, the perovskite material may comprise the empirical formula C2MX4, wherein: C comprises one or more of the above-described cations, Group 1 metals, Group 2 metals and / or other cations or cation-like compounds; M comprises one or more metals (examples include Be, Mg, Ca, Sr, Ba, Fe, Cd, Co, Ni, Cu, Ag, Au, Hg, Sn, Ge, Ga, Pb, In, Tl, Sb, Bi, Ti, Zn, Cd, Hg and Zr); and X comprises one or more of the above-described anions.
[0107] Perovskite materials can also contain mixed ionic formulations, where C, M, or X comprises two or more substances, such as Cs. 0.1 FA 0.9 Pb(I 0.9 Cl 0.1 )3; Rb 0.1 FA 0.9 Pb(I 0.9 Cl 0.1 3Cs 0.1 FA 0.9 PbI3; FAPb 0.5 Sn 0.5 I3; FA 0.83 Cs 0.17 Pb(I 0.6 Br 0.4 )3;FA 0.83 Cs 0.12 Rb 0.05 Pb(I 0.6 Br 0.4)3 and FA 0.85 MA 0.15 Pb(I 0.85 Br 0.15 3.
[0108] Design of composite perovskite material devices
[0109] In some embodiments, this disclosure provides a composite design of PV devices and other similar devices (e.g., batteries, hybrid PV batteries, FETs, LEDs, nonlinear optical devices (NLOs), waveguides, etc.) including one or more perovskite materials. For example, one or more perovskite materials can be used as the first and second active materials in some embodiments (e.g., Figure 3 The active materials are one or both of 3906a and 3908a. More generally, some embodiments of this disclosure provide PV devices or other devices having an active layer comprising one or more perovskite materials. In such embodiments, the perovskite material (i.e., a material comprising any one or more perovskite materials) can be used in the active layer of various structures. Furthermore, the perovskite material may have the function of any one or more components of the active layer (e.g., charge transport material, mesoporous material, photoactive material, and / or interface material, each of which will be discussed in more detail below). In some embodiments, the same perovskite material may have multiple such functions; however, in other embodiments, a variety of perovskite materials may be included in the device, each perovskite material having one or more such functions. In some embodiments, regardless of the function of the perovskite material, it may be prepared and / or present in the device in various states. For example, in some embodiments, it may be substantially solid. Solutions or suspensions may be coated or otherwise deposited within the device (e.g., on another part of the device, such as a mesoporous layer, interface layer, charge transport layer, photoactive layer, or other layer, and / or on electrodes). In some implementations, the perovskite material can be formed in situ on the surface of another component of the device (e.g., by vapor deposition as a thin film solid). Any other suitable means can be used to form a layer containing perovskite material.
[0110] Typically, perovskite material devices may include a first electrode, a second electrode, and an active layer comprising a perovskite material, the active layer being at least partially disposed between the first and second electrodes. In some embodiments, the first electrode may be one of an anode and a cathode, and the second electrode may be the other of an anode and a cathode. The active layer according to some embodiments may include any one or more active layer components, including any one or more of the following: charge transport materials; liquid electrolytes; mesoporous materials; photoactive materials (e.g., dyes, silicon, cadmium telluride, cadmium sulfide, cadmium selenide, copper indium gallium selenide, gallium arsenide, germanium indium phosphide, semiconductor polymers, other photoactive materials); and interface materials. Any one or more of these active layer components may include one or more perovskite materials. In some embodiments, some or all of the active layer components may be wholly or partially disposed in sublayers. For example, the active layer may include any one or more of the following: an interface layer comprising an interface material; a mesoporous layer comprising a mesoporous material; and a charge transport layer comprising a charge transport material. Furthermore, an interface layer may be included between any two or more other layers of the active layer according to some embodiments and / or between the active layer components and the electrodes. The layers mentioned herein may include final settings (e.g., substantially separate portions of each material identifiable individually within a device), and / or the mention of a layer may mean a setting during device fabrication, although subsequent mixing of materials may occur within each layer. In some embodiments, layers may be discrete and contain substantially continuous materials (e.g., layers may be as follows). Figure 2 (As shown).
[0111] In some embodiments, the perovskite device can be a field-effect transistor (FET). A FET perovskite device can include a source electrode, a drain electrode, a gate electrode, a dielectric layer, and a semiconductor layer. In some embodiments, the semiconductor layer of the FET perovskite device can be made of perovskite material.
[0112] Perovskite material devices according to some embodiments may optionally include one or more substrates. In some embodiments, one or both of the first and second electrodes may be coated or otherwise disposed on the substrate such that the electrode is substantially disposed between the substrate and the active layer. In various embodiments, the materials constituting the device (e.g., substrate, electrodes, active layer, and / or active layer components) may be wholly or partially rigid or flexible. In some embodiments, the electrodes may act as substrates, thereby eliminating the need for a separate substrate.
[0113] Furthermore, perovskite material devices according to certain embodiments may optionally include an anti-reflective layer or an anti-reflective coating (ARC). Additionally, perovskite material devices may include any one or more additives, such as any one or more additives discussed above with respect to some embodiments of this disclosure.
[0114] Partial reference Figure 2 Describe some of the various materials that may be included in perovskite material devices. Figure 2 This is a schematic diagram of a perovskite material device 3900 according to some implementation schemes. Although the various components of device 3900 are shown as discrete layers comprising continuous material, it should be understood that... Figure 2 This is a stylized diagram; therefore, embodiments thereof may include such discrete layers and / or discontinuous layers that are substantially mixed with each other, consistent with the use of the term "layer" discussed earlier herein. Device 3900 includes a first substrate 3901 and a second substrate 3913. A first electrode 3902 is disposed on the inner surface of the first substrate 3901, and a second electrode 3912 is disposed on the inner surface of the second substrate 3913. An active layer 3950 is sandwiched between the two electrodes 3902 and 3912. The active layer 3950 includes a mesoporous layer 3904; first and second photoactive materials 3906 and 3908; a charge transport layer 3910; and several interface layers. Figure 2 An example device 3900 according to an embodiment is further shown, wherein sublayers of the active layer 3950 are separated by interface layers, and wherein the interface layers are disposed on each electrode 3902 and 3912. Specifically, second, third, and fourth interface layers 3905, 3907, and 3909 are disposed between each of the mesoporous layer 3904, the first photoactive material 3906, the second photoactive material 3908, and the charge transport layer 3910. First and fifth interface layers 3903 and 3911 are disposed between (i) the first electrode 3902 and the mesoporous layer 3904; and (ii) the charge transport layer 3910 and the second electrode 3912, respectively. Therefore, Figure 2 The structure of the illustrated example device can be characterized as: substrate—electrode—active layer—electrode—substrate. The structure of the active layer 3950 can be characterized as: interface layer—mesoporous layer—interface layer—photoactive material—interface layer—photoactive material—interface layer—charge transport layer—interface layer. As previously mentioned, in some embodiments, an interface layer is not required; or, one or more interface layers may be included only between some (but not all) active layer components and / or device components.
[0115] The substrate, such as one or both of the first substrate 3901 and the second substrate 3913, may be flexible or rigid. If two substrates are included, at least one substrate should be transparent or translucent to electromagnetic (EM) radiation (e.g., UV, visible, or IR radiation). If one substrate is included, it may be similarly transparent or translucent, however, it need not be, as long as a portion of the device allows EM radiation to contact the active layer 3950. Suitable substrate materials include any one or more of the following: glass; sapphire; magnesium oxide (MgO); mica; polymers (e.g., PEN, PET, PEG, polyolefins, polypropylene, polyethylene, polycarbonate, PMMA, polyamide, vinyl, Kapton); ceramics; carbon; composite materials (e.g., glass fiber, Kevlar, carbon fiber); fabrics (e.g., cotton, nylon, silk, wool); wood; drywall; tiles (e.g., ceramic, composite, or clay); metals; steel; silver; gold; aluminum; magnesium; concrete; and combinations thereof.
[0116] As previously mentioned, electrodes (e.g., Figure 2 One of the electrodes 3902 and 3912 can be an anode or a cathode. In some embodiments, one electrode can be used as a cathode and the other as an anode. One or both of electrodes 3902 and 3912 can be connected to leads, cables, wires, or other devices capable of transferring charge to and / or from device 3900. The electrodes can be made of any conductive material, and at least one electrode should be transparent or translucent to EM radiation, and / or arranged in a manner that allows EM radiation to contact at least a portion of the active layer 3950. Suitable electrode materials may include any one or more of the following: indium tin oxide or tin-doped indium oxide (ITO); fluorine-doped tin oxide (FTO); cadmium oxide (CdO); zinc indium tin oxide (ZITO); zinc aluminum oxide (AZO); aluminum (Al); gold (Au); silver (Ag); calcium (Ca); chromium (Cr); copper (Cu); magnesium (Mg); titanium (Ti); steel; carbon (and its allotropes); doped carbon (e.g., nitrogen-doped); core-shell structured nanoparticles (e.g., silicon-carbon core-shell structure); and combinations thereof.
[0117] Mesoporous materials (e.g., Figure 2The materials included in the mesoporous layer 3904 may include any porous material. In some embodiments, the pore diameter may be in the range of about 1 to about 100 nm; in other embodiments, the pore diameter may be in the range of about 2 to about 50 nm. Suitable mesoporous materials include any one or more of the following: any interface material and / or mesoporous material discussed elsewhere herein; aluminum (Al); bismuth (Bi); cerium (Ce); hafnium (Hf); indium (In); molybdenum (Mo); niobium (Nb); nickel (Ni); silicon (Si); titanium (Ti); vanadium (V); zinc (Zn); zirconium (Zr); oxides of any one or more of the above metals (e.g., aluminum oxide, cerium oxide, titanium oxide, zinc oxide, zirconium oxide, etc.); sulfides of any one or more of the above metals; nitrides of any one or more of the above metals; and combinations thereof. In some embodiments, any material disclosed herein may be a mesoporous material. In other embodiments, Figure 2 The device shown may not include a mesoporous material layer and may only include thin films or “dense” IFLs that are not mesoporous.
[0118] Photoactive materials (e.g., Figure 2 The first or second photoactive material (3906 or 3908) may include any photoactive compound, such as any one or more of the following: silicon (e.g., polycrystalline silicon, monocrystalline silicon, or amorphous silicon), cadmium telluride, cadmium sulfide, cadmium selenide, copper indium gallium selenide, copper indium selenide, copper zinc tin sulfide, gallium arsenide, germanium, germanium indium phosphide, indium phosphide, one or more semiconductor polymers (e.g., polythiophenes (e.g., poly(3-hexylthiophene) and its derivatives, or P3HT); carbazole copolymers, such as polyheptadecylcarbazole dithiophene. Fenylbenzothiadiazole and its derivatives (e.g., PCDTBT); other copolymers such as polycyclopentadithiophene-benzothiadiazole and its derivatives (e.g., PCPDTBT), polybenzodithiaphene-thienothiaphene dimethyl and its derivatives (e.g., PTB6, PTB7, PTB7-th, PCE-10); poly(triarylamine) compounds and their derivatives (e.g., PTAA); polyphenylene vinylidenes and their derivatives (e.g., MDMO-PPV, MEH-PPV) and combinations thereof.
[0119] In some embodiments, the photoactive material may alternatively or additionally comprise a dye (e.g., N719, N3, other ruthenium-based dyes). In some embodiments, the dye (of any composition) may be coated onto another layer (e.g., a mesoporous layer and / or an interface layer). In some embodiments, the photoactive material may comprise one or more perovskite materials. The perovskite-containing photoactive material may be in solid form, or in some embodiments, it may be in the form of a dye comprising a suspension or solution of the perovskite-containing material. Such solutions or suspensions may be coated onto other device components in a manner similar to other dyes. In some embodiments, solid perovskite-containing materials may be deposited by any suitable method (e.g., vapor deposition, solution deposition, direct placement of solid materials). Devices according to various embodiments may include one, two, three, or more photoactive compounds (e.g., one, two, three, or more perovskite materials, dyes, or combinations thereof). In some embodiments comprising multiple dyes or other photoactive materials, each of the two or more dyes or other photoactive materials may be separated by one or more interface layers. In some embodiments, multiple dyes and / or photoactive compounds may be at least partially mixed.
[0120] Charge transport materials (e.g., Figure 2 The charge transport material of the charge transport layer 3910 may include a solid charge transport material (i.e., commonly known as a solid electrolyte), or it may include a liquid electrolyte and / or an ionic liquid. Any of the liquid electrolyte, ionic liquid, and solid charge transport material may be referred to as a charge transport material. As used herein, “charge transport material” means any material, solid, liquid, or otherwise, capable of collecting and / or transporting charge carriers. For example, in a PV device according to some embodiments, the charge transport material may be capable of transporting charge carriers to the electrodes. Charge carriers may include holes (whose transport may aptly label the charge transport material as a “hole transport material”) and electrons. Holes may be transported to the anode and electrons to the cathode, depending on the location of the charge transport material relative to the cathode or anode in the PV or other device. Suitable examples of charge transport materials according to some embodiments may include any one or more of the following: perovskite materials; I - / I3 -Cobalt complexes; polythiophenes (e.g., poly(3-hexylthiophene) and its derivatives, or P3HT); carbazole copolymers, such as polyheptadecylcarbazole-dithiophene-benzothiadiazole and its derivatives (e.g., PCDTBT); other copolymers, such as polycyclopentadithiophene-benzothiadiazole and its derivatives (e.g., PCPDTBT), polybenzodithiophene-thienothiophene dimethyl and its derivatives (e.g., PTB6, PTB7, PTB7-th, PCE-10); poly(triarylamine) compounds and their derivatives (e.g., PTAA); spiro-OMeTAD; polyphenylene vinylidene and its derivatives (e.g., MDMO-PPV, MEH-PPV); fullerenes and / or fullerene derivatives (e.g., C60, PCBM); carbon nanotubes; graphite; graphene; carbon black; amorphous carbon; glassy carbon; carbon fibers; and combinations thereof. In some embodiments, the charge transport material may comprise any material (solid or liquid) capable of collecting charge carriers (electrons or holes) and / or transporting charge carriers. Therefore, the charge transport material in some embodiments may be n-type or p-type active, bipolar, and / or intrinsic semiconductor materials. The charge transport material may be disposed close to one of the electrodes of the device. In some embodiments, it may be disposed adjacent to the electrode; however, in other embodiments, an interface layer (e.g., ...) may be disposed between the charge transport material and the electrode. Figure 2 As shown, the fifth interface layer 3911). In some embodiments, the type of charge transport material can be selected based on its proximity to the electrode. For example, if the charge transport material collects and / or transports holes, it can be located near the anode to transport holes to the anode. However, the charge transport material can be placed near the cathode and selected or configured to transport electrons to the cathode.
[0121] As previously mentioned, devices according to various embodiments may optionally include an interface layer between any two other layers and / or materials; however, devices according to some embodiments do not require any interface layer. Thus, for example, perovskite material devices may include zero, one, two, three, four, five, or more interface layers (e.g., Figure 2Example devices include five interface layers 3903, 3905, 3907, 3909, and 3911. The interface layers may include thin-coated interface layers according to embodiments previously discussed herein (e.g., comprising alumina and / or other metal oxide particles, and / or a titanium oxide / metal oxide bilayer, and / or other compounds according to thin-coated interface layers discussed elsewhere herein). Interface layers according to some embodiments may include any suitable material for enhancing charge transport and / or collection between the two layers or materials; it also helps prevent or reduce the likelihood of charge recombination once charge has been transported away from one of the materials adjacent to the interface layer. Suitable interface materials may include any one or more of the following: any mesoporous materials and / or interface materials discussed elsewhere herein; Ag; Al; Au; B; Bi; Ca; Cd; Ce; Co; Cu; Fe; Ga; Ge; H; In; Mg; Mn; Mo; Nb; Ni; Pt; Sb; Sc; Si; Sn; Ta; Ti; V; W; Y; Zn; Zr; carbides of any of the above metals (e.g., SiC, Fe3C, WC); silicides of any of the above metals (e.g., Mg2Si, SrSi2, Sn2Si); oxides of any of the above metals (e.g., alumina, silicon oxide, titanium oxide, SnO2, ZnO); sulfides of any of the above metals (e.g., CdS, MoS2, SnS2); nitrides of any of the above metals (e.g., Mg3N2, TiN, BN, Si3N4); selenides of any of the above metals (e.g., Cd Se, FeSe2, ZnSe); tellurides of any of the above metals (e.g., CdTe, TiTe2, ZnTe); phosphides of any of the above metals (e.g., InP, GaP); arsenides of any of the above metals (e.g., CoAs3, GaAs, InGaAs, NiAs); antimonides of any of the above metals (e.g., AlSb, GaSb, InSb); halides of any of the above metals (e.g., CuCl, CuI, BiI3); pseudohalides of any of the above metals (e.g., CuSCN, AuCN2); carbonates of any of the above metals (e.g., CaCO3, Ce2(CO3)3); functionalized or non-functionalized alkylsilyl groups; graphite; graphene; fullerene; carbon nanotubes; any mesoporous materials and / or interface materials discussed elsewhere herein; and combinations thereof (in some embodiments, including bilayer, trilayer, or multilayer combinations). In some embodiments, the interface layer may comprise a perovskite material. Furthermore, the interface layer may include any doped embodiment of the interface material mentioned herein (e.g., Y-doped ZnO, N-doped single-walled carbon nanotubes). The interface layer may also include a compound having three of the above materials (e.g., CuTiO3, Zn2SnO4) or a compound having four of the above materials (e.g., CoNiZnO).
[0122] As an example, Figure 3 An embodiment of the perovskite material device 3900a is shown, which has the same characteristics as... Figure 2 The structure is similar to that of the perovskite material device 3900 shown. Figure 3 This is a schematic diagram of a perovskite material device 3900a according to some implementation schemes. Although the various components of device 3900a are shown as discrete layers comprising continuous material, it should be understood that... Figure 3 It is a stylized diagram; therefore, its implementation may include such discrete layers, and / or substantially mixed, discontinuous layers, consistent with the use of “layer” discussed earlier herein. Figure 3 This includes active layers 3906a and 3908a. In some embodiments, one or both of active layers 3906a and 3908a may include the components described above. Figure 2 Any perovskite photoactive material described herein. In other embodiments, one or both of active layers 3906a and 3908a may comprise any photoactive material described herein, such as thin-film semiconductors (e.g., CdTe, CZTS, CIGS), photoactive polymers, dye-sensitized photoactive materials, fullerenes, small-molecule photoactive materials, and crystalline and polycrystalline semiconductor materials (e.g., silicon, GaAs, InP, Ge). In yet another embodiment, one or both of active layers 3906a and 3908a may comprise a light-emitting diode (LED), a field-effect transistor (FET), a thin-film battery layer, or a combination thereof. In embodiments, one of active layers 3906a and 3908a may comprise a photoactive material, while the other may comprise a light-emitting diode (LED), a field-effect transistor (FET), a thin-film battery layer, or a combination thereof. For example, active layer 3908a may comprise a perovskite photoactive layer, and active layer 3906b may comprise a field-effect transistor layer. Figure 3 The other layers shown, such as layers 3901a, 3902a, 3903a, 3904a, 3905a, 3907a (i.e., composite layers), 3909a, 3910a, 3911a, 3912a, and 3913a, can be similar to those described in this paper. Figure 2 The corresponding layers described above.
[0123] Furthermore, in some embodiments, the perovskite material may have three or more active layers. For example, Figure 4 It shows having with Figure 2 An embodiment of a perovskite material device 3900b with a similar structure to the perovskite material device 3900 shown. Figure 3 This is a schematic diagram of a perovskite material device 3900b according to some implementation schemes. Although the components of device 3900b are shown as discrete layers comprising continuous material, it should be understood that... Figure 4It is a stylized diagram; therefore, its implementation may include such discrete layers, and / or substantially mixed, discontinuous layers, consistent with the use of “layer” discussed earlier in this document. Figure 4 This includes active layers 3904b, 3906b, and 3908b. In some embodiments, one or more of the active layers 3904b, 3906b, and 3908b may include the features described above. Figure 2 Any perovskite photoactive material described herein. In other embodiments, one or more of the active layers 3904b, 3906b, and 3908b may comprise any photoactive material described herein, such as thin-film semiconductors (e.g., CdTe, CZTS, CIGS), photoactive polymers, dye-sensitized photoactive materials, fullerenes, small-molecule photoactive materials, and crystalline and polycrystalline semiconductor materials (e.g., silicon, GaAs, InP, Ge). In further embodiments, one or more of the active layers 3904b, 3906b, and 3908b may comprise a light-emitting diode (LED), a field-effect transistor (FET), a thin-film battery layer, or a combination thereof. In one embodiment, one or more of the active layers 3904b, 3906b, and 3908b may comprise a photoactive material, and another may comprise a light-emitting diode (LED), a field-effect transistor (FET), a thin-film battery layer, or a combination thereof. For example, active layers 3908a and 3906b may both comprise perovskite material photoactive layers, and active layer 3904b may comprise a field-effect transistor layer. Figure 3 The other layers shown, such as layers 3901b, 3902b, 3903b, 3904b, 3905b (i.e., composite layer), 3907b (i.e., composite layer), 3909b, 3910b, 3911b, 3912b, and 3913b, can be similar to those described herein. Figure 2 The corresponding layers described above.
[0124] Further, more specific example implementations of perovskite devices will be discussed based on a more stylized description of the example device. Similarly, these descriptions are... Figure 1-4 The stylized nature of the program is not intended to limit it to certain implementation schemes. Figure 1-4 The type of device constructed from any one or more of these. In other words, it can be adjusted. Figure 1-4 The structures shown herein are intended to provide BHJ, batteries, FETs, hybrid PV batteries, series-connected multi-cell PVs, parallel-connected multi-cell PVs, and other similar devices according to any suitable means (including those expressly discussed elsewhere herein, and other suitable means that will be clear to those skilled in the art to understand this disclosure).
[0125] Formulation of active layer of perovskite material
[0126] As mentioned above, in some embodiments, the perovskite material in the active layer may have the chemical formula CMX. 3-y X' y (0≥y≥3), wherein: C comprises one or more cations (e.g., amines, ammonium, Group 1 metals, Group 2 metals, formamidinium, guanidine, ethylenetetramine, phosphonium, imidazolium, and / or other cations or cationic compounds); M comprises one or more metals (e.g., Be, Mg, Ca, Sr, Ba, Fe, Cd, Co, Ni, Cu, Ag, Au, Hg, Sn, Ge, Ga, Pb, In, Tl, Sb, Bi, Ti, Zn, Cd, Hg, and Zr); and X and X' comprise one or more anions. In one embodiment, the perovskite material may include CPbI 3- y Cl y In some implementations, perovskite material can be deposited onto a substrate as an active layer in a PV device using, for example, drop coating, spin coating, slot die printing, screen printing, or inkjet printing, following the steps described below.
[0127] First, a lead halide precursor ink is formed. A controlled atmosphere can be created by collecting a quantity of lead halide in a clean, dry container (e.g., a controlled atmosphere chamber with a glove-covered opening allows for handling of the material in an airless environment). Suitable lead halides include, but are not limited to, lead(II) iodide, lead(II) bromide, lead(II) chloride, and lead(II) fluoride. Lead halides may comprise a single type of lead halide, or they may comprise a mixture of lead halide in precise proportions. In some embodiments, the lead halide mixture may contain 0.001-100 mol% of an iodide, bromide, chloride, or fluoride in any binary, ternary, or quaternary ratio. In one embodiment, the lead halide mixture may contain lead(II) chloride and lead(II) iodide in a ratio of about 10:90 mol:mol. In other embodiments, the lead halide mixture may contain lead(II) chloride and lead(II) iodide in a ratio of about 5:95, about 7.5:92.5, or about 15:85 mol:mol.
[0128] Alternatively, other lead salt precursors can be used in combination with or as a substitute for lead halide salts to form precursor inks. Suitable precursor salts may contain lead(II) or lead(IV) and any combination of the following anions: nitrate, nitrite, carboxylate, acetate, pyruvate, formate, oxalate, sulfate, sulfite, thiosulfate, phosphate, tetrafluoroborate, hexafluorophosphate, tetra(perfluorophenyl)borate, hydride, oxide, peroxide, hydroxide, nitride, arsenate, arsenite, perchlorate, carbonate, bicarbonate, chromate, dichromate, iodate, bromate, chlorate, chlorite, hypochlorite, hypobromite, cyanide, cyanate, isocyanate, fulminate, thiocyanate, isothiocyanate, azide, tetracarbonylcobaltate, carbamoyl dicyanomethane, dicyanonitromethane, dicyanamide, tricyanomethane, amide, and permanganate.
[0129] The precursor ink may also contain lead(II) or lead(IV) salts in a molar ratio of 0 to 100% with the following metal ions: Be, Mg, Ca, Sr, Ba, Fe, Cd, Co, Ni, Cu, Ag, Au, Hg, Sn, Ge, Ga, Pb, In, Tl, Sb, Bi, Ti, Zn, Cd, Hg, and Zr, as salts of the above anions.
[0130] A solvent can then be added to the container to dissolve the solid lead, thereby forming a lead halide precursor ink. Suitable solvents include, but are not limited to: anhydrous N-cyclohexyl-2-pyrrolidone, alkyl-2-pyrrolidone, dimethylformamide, dialkylformamide, dimethyl sulfoxide (DMSO), methanol, ethanol, propanol, butanol, tetrahydrofuran, formamide, tert-butylpyridine, pyridine, alkylpyridine, pyrrolidine, chlorobenzene, dichlorobenzene, dichloromethane, chloroform, and combinations thereof. In one embodiment, the solid lead is dissolved in anhydrous dimethylformamide (DMF). The solid lead can be dissolved at a temperature between about 20°C and about 150°C. In one embodiment, the solid lead is dissolved at about 85°C. The solid lead can be dissolved for the required duration to form a solution, which can occur over a period of up to about 72 hours. The resulting solution forms the matrix of the lead halide precursor ink. In some embodiments, the lead halide precursor ink may have a lead halide concentration of about 0.001 M to about 10 M. In one embodiment, the lead halide precursor ink has a lead halide concentration of approximately 1 M.
[0131] Optionally, certain additives may be added to the lead halide precursor ink to influence the crystallinity and stability of the final perovskite. In some embodiments, the lead halide precursor ink may also contain amino acids (e.g., 5-aminovaleric acid, histidine, glycine, lysine), amino acid hydrohalides (e.g., hydrochloride of 5-aminovaleric acid), IFL surface modifiers (SAM) (e.g., those discussed above in this specification), or combinations thereof. Amino acids suitable for lead halide precursor inks may include, but are not limited to, α-amino acids, β-amino acids, γ-amino acids, δ-amino acids, and any combination thereof. In one embodiment, formamidine chloride may be added to the lead halide precursor ink. In other embodiments, any cationic halide discussed above in this specification may be used. In some embodiments, combinations of additives may be added to the lead halide precursor ink, including, for example, a combination of formamidine chloride and 5-aminovaleric acid salt.
[0132] As an explanation, and without limiting this disclosure to any particular theory or mechanism, it has been found that formamidinium chloride and 5-aminovaleric acid can improve the stability of perovskite PV devices when used as additives or countercations in one-step perovskite device fabrication. It has also been found that chlorides in the form of PbCl2 can improve the performance of perovskite PV devices when added to a PbI2 precursor solution in a two-step process. It has been found that two-step perovskite thin film deposition processes can be improved by directly adding formamidinium chloride and / or 5-aminovaleric acid salt to a lead halide precursor solution (e.g., PbI2) to take advantage of both materials. Other perovskite film deposition processes can also be improved by adding formamidinium chloride, 5-aminovaleric acid salt, or PbCl2 to a lead halide precursor solution.
[0133] Depending on the desired properties of the resulting perovskite material, additives (including formamidinium chloride and / or 5-aminovalerate) can be added to the lead halide precursor ink at various concentrations. In one embodiment, the additive can be added at a concentration of about 1 nM to about 1 M. In another embodiment, the additive can be added at a concentration of about 1 μM to about 1 M. In yet another embodiment, the additive can be added at a concentration of about 1 μM to about 1 mM.
[0134] Optionally, in some embodiments, water may be added to the lead halide precursor ink. For explanation purposes, and without limiting the invention to any particular theory or mechanism, the presence of water affects the crystal growth of perovskite thin films. Under normal conditions, water may be absorbed from the air in the form of vapor. However, it is possible to control the crystallinity of perovskite PVs by adding water directly to a specific concentration of the lead halide precursor ink. Suitable water includes distilled water, deionized water, or any other water source that is substantially free of contaminants (including minerals). Based on optical IV scanning, it has been found that the photoelectric conversion efficiency of perovskite PVs with added water can be nearly three times that of completely dry devices.
[0135] Depending on the desired properties of the resulting perovskite material, water can be added to the lead halide precursor ink at various concentrations. In one embodiment, water can be added at a concentration of about 1 nL / mL to about 1 mL / mL. In another embodiment, water can be added at a concentration of about 1 μL / mL to about 0.1 mL / mL. In yet another embodiment, water can be added at a concentration of about 1 μL / mL to about 20 μL / mL.
[0136] The lead halide precursor ink can then be deposited on a desired substrate. Suitable substrates may include any substrates identified above in this disclosure. As described above, the lead halide precursor ink can be deposited by a variety of methods, including but not limited to: drop coating, spin coating, slot die printing, screen printing, or inkjet printing. In some embodiments, the lead halide precursor ink can be spin-coated onto the substrate at a speed of about 500 rpm to about 10,000 rpm for a duration of about 5 seconds to about 600 seconds. In one embodiment, the lead halide precursor ink can be spin-coated onto the substrate at about 3,000 rpm for about 30 seconds. The lead halide precursor ink can be deposited onto the substrate in an ambient atmosphere with a humidity range of about 0% relative humidity to about 50% relative humidity. The lead halide precursor ink can then be dried in a substantially anhydrous atmosphere (i.e., less than 30% relative humidity) to form a thin film.
[0137] The film can then be thermally annealed at a temperature of about 20°C to about 300°C for a period of up to about 24 hours. In one embodiment, the film can be thermally annealed at a temperature of about 50°C for about 10 minutes. The perovskite material active layer can then be completed by a conversion process in which the precursor film is immersed or rinsed with a solution containing a solvent or solvent mixture (e.g., DMF, isopropanol, methanol, ethanol, butanol, chloroform, chlorobenzene, dimethyl sulfoxide, water) and salts with concentrations between 0.001M and 10M (e.g., methylammonium iodide, formamidinium iodide, guanidinium iodide, 1,2,2-triaminovinylammonium iodide, 5-aminovalerate hydroiodate). In some embodiments, the film can also be thermally tempered in the same manner as described in the first line of this paragraph.
[0138] In some embodiments, lead salt precursors can be deposited on a substrate to form a lead salt film. The substrate temperature can be approximately equal to ambient temperature or have a controlled temperature between 0°C and 500°C. Lead salt precursors can be deposited by a variety of methods known in the art, including but not limited to spin coating, slot die printing, inkjet printing, gravure printing, screen printing, sputtering, PE-CVD, thermal evaporation, and spraying. In some embodiments, the deposition of lead salt precursors may include sheet-to-sheet or roll-to-roll manufacturing methods. The deposition of lead salt precursors can be carried out in a variety of atmospheres at ambient pressure (e.g., about one atmosphere, depending on altitude and atmospheric conditions) or below atmospheric or ambient pressure (e.g., 1 mTorr to 500 mTorr). The deposition atmosphere may include ambient air, a controlled humidity environment (e.g., 0-100 g H2O / m³), or a controlled humidity environment. 3 The gas can be pure argon, pure nitrogen, pure oxygen, pure hydrogen, pure helium, pure neon, pure krypton, pure CO2, or any combination of the above gases. The controlled humidity environment can include an environment where the absolute humidity or % relative humidity is maintained at a fixed value, or an environment where the absolute humidity or % relative humidity varies according to a predetermined set point or a predetermined function. In a particular embodiment, deposition can occur in a controlled humidity environment with a relative humidity % greater than or equal to 0% and less than or equal to 50%. In other embodiments, deposition can occur in an environment containing greater than or equal to 0 g H2O / m³. 3 Gases and less than or equal to 20g H2O / m 3 It occurs in a controlled humidity environment for the gas.
[0139] Lead salt precursors can be liquids, gases, solids, or combinations of these states, such as solutions, suspensions, colloids, foams, gels, or aerosols. In some embodiments, the lead salt precursor can be a solution containing one or more solvents. For example, the lead salt precursor may contain one or more of the following: N-cyclohexyl-2-pyrrolidone, alkyl-2-pyrrolidone, dimethylformamide, dialkylformamide, dimethyl sulfoxide (DMSO), acetonitrile, methanol, ethanol, propanol, butanol, tetrahydrofuran, formamide, tert-butylpyridine, pyridine, alkylpyridine, pyrrolidine, chlorobenzene, dichlorobenzene, dichloromethane, chloroform, and combinations thereof. Lead salt precursors may comprise a single lead salt (e.g., lead(II) iodide, lead(II) thiocyanate, or any combination of lead salts disclosed herein (e.g., PbI₂ + PbCl₂; PbI₂ + Pb(SCN)₂). Lead salt precursors may also contain one or more additives, such as amino acids (e.g., 5-aminovalerate hydroiodide), 1,8-diiodooctane, 1,8-dithiooctane, formamidinium halides, acetic acid, trifluoroacetic acid, methyl ammonium halide, or water. Lead halide precursor inks are permitted. The film is dried in a substantially anhydrous atmosphere (i.e., relative humidity less than 30%) to form a thin film. The film can then be thermally annealed at a temperature of about 20°C to about 300°C for about 24 hours. Annealing can be carried out at ambient pressure (e.g., about one atmosphere, depending on altitude and atmospheric conditions) or at pressures below atmospheric or ambient (e.g., 1 mTorr to 500 mTorr) in a variety of atmospheres. Annealing atmospheres can include ambient air, controlled humidity environments (e.g., 0-100 g H₂O / m³), etc. 3 The controlled humidity environment may consist of pure argon, pure nitrogen, pure oxygen, pure hydrogen, pure helium, pure neon, pure krypton, pure CO2, or any combination thereof. The controlled humidity environment may include an environment where the absolute humidity or % relative humidity is maintained at a fixed value, or an environment where the absolute humidity or % relative humidity varies according to a predetermined set point or a predetermined function. In a particular embodiment, annealing may occur in a controlled humidity environment with a % relative humidity greater than or equal to 0% and less than or equal to 50%. In other embodiments, annealing may occur in an environment containing greater than or equal to 0 g H2O / m³. 3 Gases and less than or equal to 20g H2O / m 3 It occurs in a controlled humidity environment for the gas.
[0140] Following the deposition of the lead salt precursor, a second salt precursor (e.g., formamidinium iodide, formamidinium thiocyanate, guanidinium thiocyanate) can be deposited on the lead salt film, wherein the temperature of the lead salt film can be approximately equal to ambient temperature or have a controlled temperature ranging from 0°C to 500°C. In some embodiments, the second salt precursor can be deposited at ambient temperature or at an elevated temperature of approximately 25°C to 125°C. The second salt precursor can be deposited by a variety of methods known in the art, including but not limited to spin coating, slot die printing, inkjet printing, gravure printing, screen printing, sputtering, PE-CVD, thermal evaporation, or spraying. The deposition of the second salt precursor can be carried out in a variety of atmospheres at ambient pressure (e.g., approximately one atmosphere, depending on altitude and atmospheric conditions) or below atmospheric or ambient pressure (e.g., 1 mTorr to 500 mTorr). The deposition atmosphere can include ambient air, a controlled humidity environment (e.g., 0-100 g H2O / m³), or a controlled humidity environment. 3 The gas can be pure argon, pure nitrogen, pure oxygen, pure hydrogen, pure helium, pure neon, pure krypton, pure CO2, or any combination of the above gases. The controlled humidity environment can include an environment where the absolute humidity or % relative humidity is maintained at a fixed value, or an environment where the absolute humidity or % relative humidity varies according to a predetermined setpoint or predetermined function. In a particular embodiment, deposition can occur in a controlled humidity environment with a relative humidity % greater than or equal to 0% and less than or equal to 50%. In other embodiments, deposition can occur in an environment containing greater than or equal to 0 g H2O / m³. 3 Gas and less than or equal to 20g H2O / m 3 It occurs in a controlled humidity environment for the gas.
[0141] In some embodiments, the second salt precursor may be a solution containing one or more solvents. For example, the second salt precursor may comprise one or more of the following: anhydrous N-cyclohexyl-2-pyrrolidone, alkyl-2-pyrrolidone, dimethylformamide, dialkylformamide, dimethyl sulfoxide (DMSO), acetonitrile, methanol, ethanol, propanol, butanol, tetrahydrofuran, formamide, tert-butylpyridine, pyridine, alkylpyridine, pyrrolidine, chlorobenzene, dichlorobenzene, dichloromethane, chloroform, and combinations thereof.
[0142] After depositing the lead salt precursor and the second salt precursor, the substrate can be annealed. Annealing the substrate can transform the lead salt precursor and the second salt precursor into perovskite materials (e.g., FAPbI3, GAPb(SCN)3, FASnI3). Annealing can be performed in various atmospheres at ambient pressure (e.g., about one atmosphere, depending on altitude and atmospheric conditions) or at pressures below atmospheric or ambient (e.g., 1 mTorr to 500 mTorr). Annealing atmospheres can include ambient air, controlled humidity environments (e.g., 0-100 g H2O / m³). 3The controlled humidity environment may consist of pure argon, pure nitrogen, pure oxygen, pure hydrogen, pure helium, pure neon, pure krypton, pure CO2, or any combination thereof. The controlled humidity environment may include an environment where the absolute humidity or % relative humidity is maintained at a fixed value, or an environment where the absolute humidity or % relative humidity varies according to a predetermined set point or a predetermined function. In a particular embodiment, annealing may occur in a controlled humidity environment with a relative humidity % greater than or equal to 0% and less than or equal to 50%. In other embodiments, annealing may occur in an environment containing greater than or equal to 0 g H2O / m³. 3 Gases and less than or equal to 20g H2O / m 3 The annealing occurs in a controlled humidity environment of the gas. In some embodiments, the annealing may occur at a temperature greater than or equal to 50°C and less than or equal to 300°C. Unless otherwise stated, any annealing or deposition step described herein may be performed under the aforementioned conditions.
[0143] For example, in a particular embodiment, the FAPbI3 perovskite material can be formed by the following process. First, a lead(II) halide precursor comprising a molar ratio of PbI2 to PbCl2 dissolved in anhydrous DMF of approximately 90:10 can be deposited onto a substrate by spin coating or slot die printing. The lead halide precursor ink can be dried in a substantially anhydrous atmosphere (i.e., relative humidity less than 30%) for approximately one hour (±15 minutes) to form a thin film. The film can then be thermally annealed at a temperature of approximately 50°C (±10°C) for approximately ten minutes. In other embodiments, the lead halide precursor can be deposited by inkjet printing, gravure printing, screen printing, sputtering, PE-CVD, atomic layer deposition, thermal evaporation, or spraying. Next, the formamidinium iodide precursor, comprising a concentration of 25-60 mg / mL of formamidinium iodide dissolved in anhydrous isopropanol, can be deposited onto a lead halide film by spin coating or slot die printing. In other embodiments, the formamidinium iodide precursor can be deposited by inkjet printing, gravure printing, screen printing, sputtering, PE-CVD, atomic layer deposition, thermal evaporation, or spraying. After depositing the lead halide precursor and the formamidinium iodide precursor, a coating can be applied at approximately 25% relative humidity (approximately 4 to 7 g H₂O / mL). 3 The substrate is annealed in air and between approximately 125°C and 200°C to form formamidinium lead iodide (FAPbI3) perovskite material.
[0144] In another embodiment, the perovskite material may comprise C'CPbX3, wherein C' is one or more Group 1 metals (i.e., Li, Na, K, Rb, Cs). In a particular embodiment, M' may be cesium (Cs). In another embodiment, C' may be rubidium (Rb). In another embodiment, C' may be sodium (Na). In another embodiment, C' may be potassium (K). In yet another embodiment, the perovskite material may include C' vC w Pb y X z Where C' is one or more Group 1 metals, and v, w, y, and z represent real numbers between 1 and 20. In some embodiments, the perovskite material can be deposited as an active layer in a PV device onto a substrate using, for example, drop coating, spin coating, gravure coating, doctor blade coating, reverse gravure coating, slot die printing, screen printing, or inkjet printing, using the steps described below.
[0145] First, a lead halide solution is formed. A certain amount of lead halide can be collected in a clean, dry container under a controlled atmosphere. Suitable lead halides include, but are not limited to, lead(II) iodide, lead(II) bromide, lead(II) chloride, and lead(II) fluoride. The lead halide may contain a single type of lead halide, or it may contain a mixture of lead halide in precise proportions. In one embodiment, the lead halide may contain lead(II) iodide. In some embodiments, the lead halide mixture may contain 0.001-100 mol% of iodide, bromide, chloride, or fluoride in any binary, ternary, or quaternary ratio. In one embodiment, the lead halide mixture may contain lead(II) chloride and lead(II) iodide in a ratio of about 10:90 mol:mol. In other embodiments, the lead halide mixture may contain lead(II) chloride and lead(II) iodide in a ratio of about 5:95, about 7.5:92.5, or about 15:85 mol:mol.
[0146] Alternatively, other lead salt precursors can be used in combination with or as a substitute for lead halide salts to form lead salt solutions. Suitable precursor lead salts may contain lead(II) or lead(IV) and any combination of the following anions: nitrate, nitrite, carboxylate, acetate, formate, oxalate, sulfate, sulfite, thiosulfate, phosphate, tetrafluoroborate, hexafluorophosphate, tetra(perfluorophenyl)borate, hydride, oxide, peroxide, hydroxide, nitride, arsenate, arsenite, perchlorate, carbonate, bicarbonate, chromate, dichromate, iodate, bromate, chlorate, chlorite, hypochlorite, hypobromate, cyanide, cyanate, isocyanate, fulminate, thiocyanate, isothiocyanate, azide, tetracarbonylcobaltate, carbamoyl dicyanomethane, dicyanonitromethane, dicyanamide, tricyanomethane, amide, and permanganate.
[0147] The lead salt solution may also contain lead(II) or lead(IV) salts in molar ratios of 0 to 100% with the following metal ions: Be, Mg, Ca, Sr, Ba, Fe, Cd, Co, Ni, Cu, Ag, Au, Hg, Sn, Ge, Ga, Pb, In, Tl, Sb, Bi, Ti, Zn, Cd, Hg, and Zr, as salts of the above anions.
[0148] A solvent can then be added to the container to dissolve the solid lead halide to form a lead halide solution. Suitable solvents include, but are not limited to: anhydrous N-cyclohexyl-2-pyrrolidone, alkyl-2-pyrrolidone, dimethylformamide (DMF), dialkylformamide, dimethyl sulfoxide (DMSO), acetonitrile, methanol, ethanol, propanol, butanol, tetrahydrofuran, formamide, tert-butylpyridine, pyridine, alkylpyridine, pyrrolidine, chlorobenzene, dichlorobenzene, dichloromethane, chloroform, and combinations thereof. In one embodiment, the solid lead is dissolved in anhydrous dimethylformamide (DMF). The solid lead halide can be dissolved at a temperature of about 20°C to about 150°C. In one embodiment, the solid lead halide is dissolved at about 85°C. The solid lead halide can be dissolved for the required duration to form a solution, which can occur over a period of up to about 72 hours. The resulting solution forms the matrix of the lead halide precursor ink. In some embodiments, the lead halide concentration of the lead halide precursor ink can be from about 0.001M to about 10M. In one embodiment, the lead halide concentration of the lead halide precursor ink is about 1M. In some embodiments, the lead halide solution may also contain amino acids (e.g., 5-aminovaleric acid, histidine, glycine, lysine), amino acid hydrohalides (e.g., hydrochloride of 5-aminovaleric acid), IFL surface modifiers (SAM) (e.g., those discussed above in this specification), or combinations thereof.
[0149] Next, a Group 1 metal halide solution is formed. A certain amount of Group 1 metal halides can be collected in a clean, dry container under a controlled atmosphere. Suitable Group 1 metal halides include, but are not limited to: cesium iodide, cesium bromide, cesium chloride, cesium fluoride, rubidium iodide, rubidium bromide, rubidium chloride, rubidium fluoride, lithium iodide, lithium bromide, lithium chloride, lithium fluoride, sodium iodide, sodium bromide, sodium chloride, sodium fluoride, potassium iodide, potassium bromide, potassium chloride, and potassium fluoride. The Group 1 metal halide may include a single type of Group 1 metal halide, or it may include a mixture of Group 1 metal halides in precise proportions. In one embodiment, the Group 1 metal halide may include cesium iodide. In another embodiment, the Group 1 metal halide may include rubidium iodide. In another embodiment, the Group 1 metal halide may include sodium iodide. In another embodiment, the Group 1 metal halide may include potassium iodide.
[0150] Alternatively, other Group 1 metal salt precursors can be used in combination with or as a substitute for Group 1 metal halide salts to form Group 1 metal salt solutions. Suitable precursor group 1 metal salts may contain any combination of group 1 metals and the following anions: nitrate, nitrite, carboxylate, acetate, formate, oxalate, sulfate, sulfite, thiosulfate, phosphate, tetrafluoroborate, hexafluorophosphate, tetra(perfluorophenyl)borate, hydride, oxide, peroxide, hydroxide, nitride, arsenate, arsenite, perchlorate, carbonate, bicarbonate, chromate, dichromate, iodate, bromate, chlorate, chlorite, hypochlorite, hypobromate, cyanide, cyanate, isocyanate, fulminate, thiocyanate, isothiocyanate, azide, tetracarbonylcobaltate, carbamoyl dicyanomethane, dicyanonitromethane, dicyanamide, tricyanomethane, amide, and permanganate.
[0151] A solvent can then be added to the container to dissolve the Group 1 metal halide solid to form a Group 1 metal halide solution. Suitable solvents include, but are not limited to: anhydrous N-cyclohexyl-2-pyrrolidone, alkyl-2-pyrrolidone, dimethylformamide (DMF), dialkylformamide, dimethyl sulfoxide (DMSO), acetonitrile, methanol, ethanol, propanol, butanol, tetrahydrofuran, formamide, tert-butylpyridine, pyridine, alkylpyridine, pyrrolidine, chlorobenzene, dichlorobenzene, dichloromethane, chloroform, and combinations thereof. In one embodiment, the lead solid is dissolved in anhydrous dimethyl sulfoxide (DMSO). The Group 1 metal halide solid can be dissolved at a temperature of about 20°C to about 150°C. In one embodiment, the Group 1 metal halide solid is dissolved at room temperature (i.e., about 25°C). The Group 1 metal halide solid can be dissolved for the required duration to form a solution, which can occur over a period of up to about 72 hours. The resulting solution forms a Group 1 metal halide solution. In some embodiments, the Group 1 metal halide solution may have a Group 1 metal halide concentration of about 0.001 M to about 10 M. In one embodiment, the Group 1 metal halide solution has a Group 1 metal halide concentration of about 1 M. In some embodiments, the Group 1 metal halide solution may also contain amino acids (e.g., 5-aminovaleric acid, histidine, glycine, lysine), amino acid hydrohalides (e.g., hydrochloride of 5-aminovaleric acid), IFL surface modifiers (SAM) (e.g., those discussed above in this specification), or combinations thereof.
[0152] Next, the lead halide solution and the Group 1 metal halide solution are mixed to form a film precursor ink. The lead halide solution and the Group 1 metal halide solution can be mixed in a certain proportion such that the resulting film precursor ink has a Group 1 metal halide molar concentration of 0% to 25% lead halide molar concentration. In a specific embodiment, the film precursor ink has a Group 1 metal halide molar concentration of 1% lead halide. In a specific embodiment, the film precursor ink has a Group 1 metal halide molar concentration of 5% lead halide. In a specific embodiment, the film precursor ink has a Group 10 metal halide molar concentration of 10% lead halide. In a specific embodiment, the film precursor ink has a Group 15 metal halide molar concentration of 15% lead halide. In a specific embodiment, the film precursor ink has a Group 10 metal halide molar concentration of 20% lead halide. In a specific embodiment, the film precursor ink has a Group 15 metal halide molar concentration of 25% lead halide. In some implementations, the lead halide solution and the Group 1 metal halide solution may be stirred or agitated during or after mixing.
[0153] The film precursor ink can then be deposited on a desired substrate. Suitable substrate layers may include any substrate layer defined for the foregoing of this disclosure. As described above, the film precursor ink can be deposited in a variety of ways, including but not limited to drop casting, spin coating, gravure coating, doctor blade coating, reverse gravure coating, slot die printing, screen printing, or inkjet printing. In some embodiments, the film precursor ink can be spin-coated onto the substrate at a speed of about 500 rpm to about 10,000 rpm for a period of about 5 seconds to about 600 seconds. In one embodiment, the film precursor ink can be spin-coated onto the substrate at about 3,000 rpm for about 30 seconds. The film precursor ink can be deposited onto the substrate in an ambient atmosphere of about 0% relative humidity to about 50% relative humidity. The film precursor ink can then be deposited in a substantially anhydrous atmosphere (i.e., relative humidity less than 30% or 7 g H2O / m³). 3 Dry in a medium to form a thin film.
[0154] The film can then be thermally annealed at a temperature of about 20°C to about 300°C for up to about 24 hours. In one embodiment, the film can be thermally annealed at a temperature of about 50°C for about 10 minutes. The perovskite material active layer can then be completed by a conversion process in which the precursor film is immersed or rinsed with a salt solution containing a solvent or solvent mixture (e.g., DMF, isopropanol, methanol, ethanol, butanol, chloroform, chlorobenzene, dimethyl sulfoxide, water) and a salt with a concentration between 0.001M and 10M (e.g., methylammonium iodide, formamidinium iodide, guanidinium iodide, 1,2,2-triaminovinylammonium iodide, hydroiodate of 5-aminovaleric acid). In some embodiments, the perovskite material film can also be thermally post-annealed in the same manner as described in the first line of this paragraph.
[0155] In some embodiments, a salt solution can be prepared by collecting salts in a clean, dry container under a controlled atmosphere. Suitable salts include, but are not limited to, methylammonium iodide, formamidinium iodide, guanidinium iodide, imidazole iodide, ethylenetetramine iodide, 1,2,2-triaminovinylammonium iodide, and hydroiodates of 5-aminovaleric acid. Other suitable salts may include any organic cations described above in the section entitled “Perovskite Materials.” The salt may comprise a single type of salt, or it may comprise a mixture of salts in precise proportions. In one embodiment, the salt may comprise methylammonium iodide. In another embodiment, the salt may comprise formamidinium iodide. Next, a solvent may be added to the container to dissolve the salt solid to form a salt solution. Suitable solvents include, but are not limited to, DMF, acetonitrile, isopropanol, methanol, ethanol, butanol, chloroform, chlorobenzene, dimethyl sulfoxide, water, and combinations thereof. In one embodiment, the formamidinium iodide salt solid is dissolved in isopropanol. The salt solid can be dissolved at a temperature of about 20°C to about 150°C. In one embodiment, the salt solid is dissolved at room temperature (i.e., about 25°C). The salt solid can dissolve for the duration required to form a solution, which can occur over a period of up to about 72 hours. The resulting solution forms a salt solution. In some embodiments, the salt concentration of the salt solution can be from about 0.001M to about 10M. In one embodiment, the salt concentration of the salt solution is about 1M.
[0156] For example, using the above method and utilizing lead(II) iodide solution, cesium iodide solution, and methylammonium (MA) iodide salt solution, a product with the formula Cs can be generated. i MA 1-i PbI3 perovskite materials, where i equals a number between 0 and 1. As another example, a perovskite material with the formula Rb can be produced using lead(II) iodide solution, rubidium iodide solution, and formamidinium (FA) iodide salt solution. i FA 1-iPbI3 perovskite materials, where i equals a number between 0 and 1. As another example, a perovskite material with the formula Cs can be produced using lead(II) iodide solution, cesium iodide solution, and formamidinium (FA) iodide salt solution. i FA 1-i PbI3 perovskite materials, where i equals a number between 0 and 1. As another example, a perovskite material with the formula K can be produced using lead(II) iodide solution, potassium iodide solution, and formamidinium (FA) iodide salt solution. i FA 1-i PbI3 perovskite materials, where i equals a number between 0 and 1. As another example, a perovskite material with the formula Na can be produced using lead(II) iodide solution, sodium iodide solution, and formamidinium (FA) iodide salt solution. i FA 1-i PbI3 perovskite materials, where i equals a number between 0 and 1. As another example, a solution of lead(II) iodide-lead(II) chloride mixture, a cesium iodide solution, and a formamidinium (FA) iodide salt solution can be used to produce a material with the formula Cs. i FA 1-i PbI 3-y Cl y The perovskite material, where i equals a number between 0 and 1, and y represents a number between 0 and 3.
[0157] In a specific embodiment, the lead halide solution described above may have a PbI2 to PbCl2 ratio of 90:10, based on the molar ratio. Cesium iodide (CsI) solution can be added to the lead halide solution using the method described above to form a thin film precursor ink with 10 mol% CsI. FAPbI3 perovskite materials can be prepared using this thin film precursor solution according to the method described above. Adding cesium ions via CsI solution as described above causes chloride anions and cesium atoms to be incorporated into the FAPbI3 lattice. This results in a greater degree of lattice shrinkage compared to adding cesium or rubidium ions without adding chloride ions as described above. Table 1 below shows the lattice parameters of FAPbI3 perovskite materials with 10 mol% rubidium and 20 mol% chloride (e.g., 10 mol% PbCl2), 10 mol% cesium, and 10 mol% cesium and 20 mol% chloride, where mol% concentration represents the additive concentration relative to lead atoms in the lead halide solution. As can be seen from Table 1, the FAPbI3 perovskite material with added cesium and chloride has a smaller lattice parameter than the other two perovskite material samples.
[0158] Table 1
[0159]
[0160] Furthermore, data show that FAPbI3 perovskite materials with added rubidium, cesium, and / or chlorides exhibit a Pm3-m cubic structure. FAPbI3 perovskites with up to 10 mol% Rb and 10 mol% Cl, or 10 mol% Cs, or 10 mol% Cs and 10 mol% Cl have been observed to maintain a cubic Pm3-m cubic crystal structure. Figure 29 The X-ray diffraction patterns corresponding to each sample shown in Table 1 are displayed. Tables 2-4 provide the X-ray diffraction peaks and intensities for the three perovskite materials shown in Table 1. This data was acquired under ambient conditions using a Cu Kα radiation source on a Rigaku Miniflex 600 at a scan rate of 1.5 degrees 2θ / min.
[0161] Table 2
[0162]
[0163] Table 3
[0164]
[0165] Table 4
[0166]
[0167] Under Cu-Kα radiation The expected X-ray diffraction patterns of cubic Pm3-m materials are shown in Table 5. From this data, it can be seen that the diffraction patterns of perovskite materials prepared with 10 mol% Rb and 10 mol% Cl, 10 mol% Cs, and 10% Cs and 10% Cl all conform to the expected patterns of cubic Pm3-m perovskite materials.
[0168] Table 5
[0169]
[0170] Enhanced perovskite
[0171] When perovskites are formulated with organic cations having alkyl chains longer than the methylammonium and formamidinium cations described herein, it is known that so-called “layered” 2D perovskites are formed. Layered 2D perovskites include structures such as the Ruddlesden-Popper phase, the Dion-Jacobson phase, and the Aurivillius phase. For example, during the formation of perovskites in a “one-step” process (not described herein), Ruddlesden-Popper 2D perovskites can be produced by replacing the aforementioned methylammonium or other cations with 1-butylammonium. In such perovskites, 1-butylammonium prevents the perovskite from forming a complete crystal lattice; instead, it causes the perovskite to form perovskite “plates” with a single-crystal structure in terms of thickness. Figure 5The structure of Ruddlesden-Popper perovskite 5500 with 1-butylammonium cation 5510 is shown. From Figure 5 It can be seen that the "tail" of the butylammonium cation 5510 causes the separation of the lead and iodide portions of the perovskite material from other lead and iodide structures, thus producing "flakes" of 2D perovskite. Therefore, if the Ruddlesden-Popper form of perovskite is not desired, the introduction of "giant organic" cations (such as 1-butylammonium or benzylammonium) during the formation of perovskite material may be undesirable.
[0172] However, adding a diluted 1-butylammonium solution before annealing the perovskite material may produce perovskites, such as... Figure 6 As shown. Figure 6 An embodiment of a perovskite material 2000 with added alkylammonium cations for surface passivation is shown. In the illustrated embodiment, the surface of formamidinium lead iodide (FAPbI3) perovskite material 2010 is shown as having 1-butylammonium cation 2020 at the surface. In some embodiments, 1-butylammonium cations or other “giant” organic cations, as described herein, may diffuse into the perovskite material near the lattice surface. In a particular embodiment, 1-butylammonium cations or other “giant” organic cations described herein may reside 50 nm or less from the lattice surface or grain boundary into the perovskite material. The presence of giant organic cations (e.g., 1-butylammonium) near or at the surface of the perovskite material can cause the chemical formula of the perovskite material to deviate from the “ideal” stoichiometry of the perovskite material disclosed herein. For example, including such organic cations can cause the perovskite material to have a chemical formula that is either substoichiometric or superstoichiometric relative to the CMX3 chemical formula described herein. In this case, the general formula of the perovskite material may be represented as C x M y X z , where x, y, and z are real numbers. In some implementations, perovskite materials can have the formula C'2C. n-1 M n X 3n+1 Where n is an integer. For example, when n = 1, perovskite materials can have the formula C'2MX4; when n = 2, perovskite materials can have the formula C'2CM2X7; and when n = 3, perovskite materials can have the formula C'2C2M3X. 10 When n=4, perovskite materials can have the formula C'2C3M4X 13 And so on. For example... Figure 30 As shown, the n-value represents the thickness of the inorganic metal halide sublattice of the perovskite material. It has the chemical formula C'₂C. n- 1M n X 3n+1The perovskite phase can form in regions where giant organic cations have diffused into or otherwise entered the perovskite lattice. For example, such a phase can exist within 50 nanometers of the lattice surface (e.g., surface or grain boundary) of an already formed perovskite material, which includes giant organic cations as disclosed herein.
[0173] The carbon "tail" of the 1-butylammonium ion provides protective properties to the perovskite surface by effectively keeping other molecules away from it. In some embodiments, the alkyl "tail" of the 1-butylammonium ion can be oriented away from or parallel to the surface of the perovskite material. In particular, the 1-butylammonium "tail" is hydrophobic, which prevents water molecules from contacting the perovskite surface and protects the surface of the perovskite material 2010 from the influence of water in the environment. Furthermore, the 1-butylammonium cation can also be used to passivate the surface of the perovskite material 2010 and any grain boundaries or defects. Passivation refers to the electrical properties that prevent charge accumulation or "trapped states" at the surface or grain boundaries of the perovskite material 2010. By using the portion used for passivation of the perovskite material 2010, 1-butylammonium can facilitate improved charge transfer into and out of the perovskite material 2010 and improve the electrical properties of the photoactive layer.
[0174] In some embodiments, other organic cations may be used instead of 1-butylammonium or in combination with 1-butylammonium. Examples of other “giant organic” organic cations that can be used for surface passivation of perovskite materials include, but are not limited to: ethylammonium, propylammonium, n-butylammonium; perylene-n-butylamineimide; butane-1,4-diammonium; 1-pentylammonium; 1-hexylammonium; poly(vinylammonium); phenethylammonium; benzylammonium; 3-phenyl-1-propanammonium; 4-phenyl-1-butylammonium; 1,3-dimethylbutylammonium; 3,3-dimethylbutylammonium; 1-heptylammonium; 1-octylammonium; 1-nonylammonium; 1-decylammonium; and 1-eicosylammonium. Furthermore, the tail of the giant organic cation contains one or more heteroatoms in addition to the cationic substance, which can be coordinated, bonded, or integrated with the perovskite material lattice. The heteroatom can be any atom in the tail that is not hydrogen or carbon, including nitrogen, sulfur, oxygen, or phosphorus.
[0175] Other examples of “giant” organic cations can include molecules functionalized with ammonium, phosphonium, or other cationic groups that can be integrated into the surface C sites of perovskite materials: benzene, pyridine, naphthalene, anthracene, xanthracene, phenanthrene, and tetraphenylene. Benzo[c]anthracene, benzo[c]phenanthrene, triphenylene, pyrene, perylene, cyclohexene, benzo[c]benzene, substituted dicarboxylic acid imide, aniline, N-(2-aminoethyl)-2-isoindole-1,3-dione, 2-(1-aminoethyl)naphthalene, 2-triphenylene-O-ethylamine ether, benzylamine, benzylammonium salt, N-n-butyl-N'-4-aminobutylperylene-3,4,9,10-bis(dicarboxyimide), 1-(4-alkylbenzene) 1-(4-alkyl-2-phenyl)ethylamine, 1-(4-alkylphenyl)methylamine, 1-(3-alkyl-5-alkylphenyl)methylamine, 1-(3-alkyl-5-alkyl-2-phenyl)ethylamine, 1-(4-alkyl-2-phenyl)ethylamine, 2-ethylamine-7-alkyl-naphthalene, 2-ethylamine-6-alkyl-naphthalene, 1-ethylamine-7-alkyl-naphthalene, 1-ethylamine-6-alkyl-naphthalene, 2- Methylamine-7-alkyl-naphthalene, 2-methylamine-6-alkyl-naphthalene, 1-methylamine-7-alkyl-naphthalene, 1-methylamine-6-alkyl-naphthalene, N-n-aminoalkyl-N'-4-aminobutylperylene-3,4,9,10-bis(dicarboximide), 1-(3-butyl-5-methoxybutylphenyl)methylamine, 1-(4-pentylphenyl)methylamine, 1-[4-(2-methylpentyl)-2-phenyl]ethylamine, 1-(3-Butyl-5-pentyl-2-phenyl)ethylamine, 2-(5-[4-methylpentyl]-2-naphthyl)ethylamine, N-7-tetrazyl-N'-4-aminobutylperylene-3,4,9,10-bis(dicarboximide), N-n-heptyl-N'-4-aminobutylperylene-3,4,9,10-bis(dicarboximide), 2-(6-[3-methoxypropyl]-2-naphthyl)ethylamine. Figure 17-28 Illustrations of the structures of these organic molecules according to certain embodiments are provided. About Figure 17 and 18 Each "R-group", R x It can be any of =H, R', Me, Et, Pr, Ph, Bz, F, Cl, Br, I, NO2, OR', NR'2, SCN, CN, N3, SR', where R' can be any of alkyl, alkenyl, or alkynyl chains. Furthermore, the R shown... x At least one of the groups can be (CH2). n EX y Or (CH2) n C(EX y )2, where n and y = 0, 1, 2 or greater, n and y may be equal or unequal, E is selected from C, Si, O, S, Se, Te, N, P, As or B, and X is a halide or pseudohalide ion, such as F, Cl, Br, I, CN, SCN or H. Furthermore, regarding Figure 19The molecule shown may include any hydrohalide of each of the amines shown, such as benzylammonium salts, wherein the X group shown may be F, Cl, Br, I, SCN, CN or any other pseudohalogen ion. Other acceptable non-halogen anions may include: nitrate, nitrite, carboxylate, acetate, pyruvate, formate, oxalate, sulfate, sulfite, thiosulfate, phosphate, tetrafluoroborate, hexafluorophosphate, tetra(perfluorophenyl)borate, hydrides, oxides, peroxides, hydroxides, nitrides, arsenate, arsenite, perchlorate, carbonate, bicarbonate, chromate, dichromate, iodate, bromate, chlorate, chlorite, hypochlorite, hypobromate, cyanide, cyanate, isocyanate, fulminate, thiocyanate, isothiocyanate, azide, tetracarbonylcobaltate, carbamoyl dicyanomethane, dicyanonitromethane, dicyanamide, tricyanomethane, amide, and permanganate. Suitable R groups may also include, but are not limited to: hydrogen, methyl, ethyl, propyl, butyl, pentyl or their isomers; any alkane, alkene or alkyne C x H y Where x = 1-20, y = 1-42, cyclic, branched, or straight-chain; haloalkane, C x H y X z x = 1-20, y = 0-42, z = 1-42, X = F, Cl, Br, or I; any aromatic group (e.g., phenyl, alkylphenyl, alkoxyphenyl, pyridine, naphthalene); cyclic complexes containing at least one nitrogen atom (e.g., pyridine, pyrrole, pyrrolidine, piperidine, tetrahydroquinoline); any sulfur-containing group (e.g., sulfoxide, thiol, alkyl sulfide); any nitrogen-containing group (nitrooxy, amine); any phosphorus-containing group (phosphate); any boron-containing group (e.g., boric acid); any organic acid (e.g., acetic acid, propionic acid); and its ester or amide derivatives; any amino acid (e.g., glycine, cysteine, proline, glutamic acid, arginine, serine, histidine, 5-ammonium valerate), including α, β, γ, and larger derivatives; any silicon-containing group (e.g., siloxane); and any alkoxy or -OC group. x H y , where x = 0-20, y = 1-42.
[0176] Furthermore, in some implementations, giant organic cations can passivate grain boundaries and surface defects in perovskite materials. Figure 7 An example embodiment of the perovskite material layer 3000 is shown, wherein 1-butylammonium 3020 passivates the surface and grain boundaries 3015 of the bulk perovskite material 3010. As described above, the alkyl tails of these ions can also form a hydrophobic layer that repels water and other polar substances, preventing these substances from reaching the surface of the perovskite material. From Figure 7As can be seen, the "tail" of a giant organic cation may not be chemically bonded (e.g., covalently or ionicly) to the surface or grain boundary 3015 of the perovskite material layer 3000. As used herein, the "tail" of any giant organic cation refers to its nonionic carbon structure. For example, the tail of 1-butylammonium is butyl, and the tail of benzylammonium is benzyl.
[0177] The tails of giant organic cations can also exhibit other arrangements relative to the surface or grain boundaries of the perovskite material. Typically, the cation "heads" of giant organic cations do not diffuse beyond the surface or grain boundaries of the perovskite material by more than 50 nanometers. The tails may interact weakly with the perovskite material and be oriented away from the grain surface. The tails may have intermolecular interactions (e.g., dipole-dipole or hydrogen bonds) with the grain surface of the perovskite material, resulting in a structure where the tails are oriented towards the grain surface. In some embodiments, the tails of some giant organic cations present in the perovskite material may not interact with the surface or grain boundaries of the perovskite material, while the tails of other giant organic cations in the perovskite material may interact with the surface or grain boundaries of the perovskite material. The tail may contain heteroatoms or anions (i.e., zwitterions) having at least one lone pair of electrons that can covalently interact with the perovskite grain surface via metal atoms (e.g., Pb, Sn, Ge, In, Bi, Cu, Ag, Au) present in the perovskite material (e.g., coordination covalent bonds). The tail may also contain cationic material, such as diammonium butane as described herein, which can be incorporated into the perovskite material by substitution at at least two “C” cation sites (e.g., formamidinium). The cationic tail can also bridge two layers of a 2D perovskite material, lying prostrate on the perovskite grain surface, or oriented away from the perovskite grain surface in a similar manner as described with respect to nonionic tails. In another embodiment, a giant organic cation (e.g., imidazolium cation) with a sufficiently large tail can simply reside on the perovskite surface or grain boundaries without diffusing into the perovskite material.
[0178] In other embodiments, giant organic cations with tail groups of varying lengths or sizes can be applied to perovskites to passivate grain boundaries and surface defects in the perovskite material. Figure 8 An exemplary embodiment of a perovskite material layer 4000 is shown, wherein a combination of 1-butylammonium 4020, 1-nonylammonium 4021, 1-heptylammonium 4022, and 1-hexylammonium 4023 passivates the surface and grain boundaries 4015 of the bulk perovskite material 4010. In a particular embodiment, any mixture of the alkylammonium compounds identified above may be applied to the perovskite material as described herein. Figure 8An exemplary embodiment of a perovskite material layer 4000 is shown, wherein a combination of 1-butylammonium 4020, 1-nonylammonium 4021, 1-heptylammonium 4022, and 1-hexylammonium 4023 passivates the surface and grain boundaries 4015 of the bulk perovskite material 4010. In certain embodiments, any mixture of the alkylammonium compounds identified above may be applied to the perovskite material as described herein. In some embodiments, the giant organic cation may include a benzyl group. Figure 8A An exemplary embodiment of a perovskite material layer 4500 is shown, having a plurality of giant organic cations containing benzyl groups, thereby passivating the surface and grain boundaries 4515 of the bulk perovskite material 4510.
[0179] As has been shown above, adding a 1-butylammonium surface coating to perovskite materials improves the high-temperature durability of perovskites in humid environments. Figure 9 This paper presents a comparison of images taken of perovskite materials with and without a 1-butylammonium (“BAI”) surface coating over a 48-day period. Both perovskite materials had the same composition and were exposed to an environment at 85°C and 55% relative humidity for 48 days. The images show that the perovskite material without the 1-butylammonium surface coating showed significant color reduction after one day of exposure, indicating significant degradation. The perovskite material with the 1-butylammonium surface coating gradually lightened in color over 48 days and retained some of its dark color after 48 days. This suggests that the perovskite material with the 1-butylammonium surface coating is more robust than the one without during prolonged exposure to high temperatures.
[0180] Figure 10 Images of perovskite materials with and without a 1-butylammonium (“BAI”) surface coating are shown as a comparison over a 7-day period. Both perovskite materials had the same composition and were exposed to an environment at 85°C and 0% relative humidity for 7 days. The images show that the perovskite material without the 1-butylammonium surface coating exhibited significant color reduction after 1 day of exposure to the same environment, indicating significant degradation. The perovskite material with the 1-butylammonium surface coating showed very little color change after 7 days. This suggests that the perovskite material with the 1-butylammonium surface coating did not completely decompose during prolonged exposure to the high temperature and humidity environment.
[0181] In other embodiments, perylene-n-butylamine-imide can be applied to the surface of the perovskite material, as described above regarding 1-butylammonium. Figure 11A -D indicates various perylene monoimides and diimides that can be applied to the surface of perovskite materials according to this disclosure. Figure 12An embodiment of perovskite material 2500 is shown, wherein an alkylammonium cation is added for surface passivation. In the illustrated embodiment, the surface of formamidinium lead iodide (FAPbI3) perovskite material 2510 is shown as having perylene-n-butylamine-imide 2520 on the surface. Figure 6 Similar to 1-butylammonium, the carbon "tail" of the perylene-n-butylamine-imide ion provides protection to the perovskite surface by effectively keeping other molecules away from the surface. Specifically, the perylene-n-butylamine-imide "tail" is hydrophobic, preventing water molecules from contacting the perovskite surface and protecting the surface of the perovskite material 2510 from the influence of water in the environment. Furthermore, the perylene-n-butylamine-imide cation can also be used to passivate the surface of the perovskite material 2510 and any grain boundaries or defects. By using this portion to passivate the perovskite material 2510, the perylene-n-butylamine-imide can facilitate improved charge transfer into and out of the perovskite material 2510 and improve the electrical properties of the photoactive layer.
[0182] The following describes an example method for depositing 1-butylammonium on perovskite materials prior to annealing.
[0183] First, a lead halide precursor ink is formed. A controlled atmosphere environment can be used to collect a quantity of lead halide in a clean, dry container (e.g., a controlled atmosphere chamber with a glove-fitting opening allows for handling of the material in an airless environment). Suitable lead halides include, but are not limited to, lead(II) iodide, lead(II) bromide, lead(II) chloride, and lead(II) fluoride. Lead halides may comprise a single type of lead halide, or they may comprise a mixture of lead halide in precise proportions. In some embodiments, the lead halide mixture may contain 0.001-100 mol% of any binary, ternary, or quaternary ratio of iodide, bromide, chloride, or fluoride. In one embodiment, the lead halide mixture may contain lead(II) chloride and lead(II) iodide in a ratio of about 10:90 mol:mol. In other embodiments, the lead halide mixture may contain lead(II) chloride and lead(II) iodide in a ratio of about 5:95, about 7.5:92.5, or about 15:85 mol:mol.
[0184] Alternatively, other lead salt precursors can be used in combination with or as a substitute for lead halide salts to form precursor inks. Suitable precursor salts may contain lead(II) or lead(IV) with any combination of the following anions: nitrate, nitrite, carboxylate, acetate, pyruvate, formate, oxalate, sulfate, sulfite, thiosulfate, phosphate, tetrafluoroborate, hexafluorophosphate, tetra(perfluorophenyl)borate, hydride, oxide, peroxide, hydroxide, nitride, arsenate, arsenite, perchlorate, carbonate, bicarbonate, chromate, dichromate, iodate, bromate, chlorate, chlorite, hypochlorite, hypobromate, cyanide, cyanate, isocyanate, fulminate, thiocyanate, isothiocyanate, azide, tetracarbonylcobaltate, carbamoyl dicyanomethane, dicyanonitromethane, dicyanamide, tricyanomethane, amide, and permanganate.
[0185] The precursor ink may also contain lead(II) or lead(IV) salts in a molar ratio of 0 to 100% to the following metal ions: Be, Mg, Ca, Sr, Ba, Fe, Cd, Co, Ni, Cu, Ag, Au, Hg, Sn, Ge, Ga, In, Tl, Sb, Bi, Ti, Zn, Cd, Hg, and Zr, as salts of the above anions.
[0186] A solvent can then be added to dissolve the solid lead, thereby forming a lead halide precursor ink. Suitable solvents include, but are not limited to: anhydrous N-cyclohexyl-2-pyrrolidone, alkyl-2-pyrrolidone, dimethylformamide, dialkylformamide, dimethyl sulfoxide (DMSO), methanol, ethanol, propanol, butanol, tetrahydrofuran, formamide, tert-butylpyridine, pyridine, alkylpyridine, pyrrolidine, chlorobenzene, dichlorobenzene, dichloromethane, chloroform, alkyl nitrile, aryl nitrile, acetonitrile, alkoxy alcohol, alkoxyethanol, 2-methoxyethanol, glycol, propylene glycol, ethylene glycol, and combinations thereof. In one embodiment, the solid lead is dissolved in anhydrous dimethylformamide (DMF). The solid lead can be dissolved at a temperature between about 20°C and about 150°C. In some embodiments, the solvent may also contain 2-methoxyethanol and acetonitrile. In some embodiments, 2-methoxyethanol and acetonitrile may be added in a volume ratio of about 25:75 to about 75:25 or at least 25:75. In some embodiments, the solvent may comprise a ratio of 2-methoxyethanol and acetonitrile to DMF of about 1:100 to about 1:1 or about 1:100 to about 1:5, based on volume. In some embodiments, the solvent may comprise a ratio of at least about 1:100 of 2-methoxyethanol and acetonitrile to DMF, based on volume. In one embodiment, the lead solid is dissolved at about 85°C. The lead solid is dissolved for the duration required to form a solution, which may occur over a period of up to about 72 hours. The resulting solution forms the matrix of the lead halide precursor ink. In some embodiments, the lead halide precursor ink may have a lead halide concentration of about 0.001M to about 10M. In one embodiment, the lead halide concentration of the lead halide precursor ink is about 1M.
[0187] Optionally, certain additives may be added to the lead halide precursor ink to influence the crystallinity and stability of the final perovskite. In some embodiments, the lead halide precursor ink may also contain amino acids (e.g., 5-aminovaleric acid, histidine, glycine, lysine), amino acid hydrohalides (e.g., hydrochloride of 5-aminovaleric acid), IFL surface modifiers (SAM) (e.g., those discussed earlier in this specification), or combinations thereof. In one embodiment, formamidinium chloride may be added to the lead halide precursor ink. In other embodiments, any cationic halide discussed earlier in this specification may be used. In some embodiments, combinations of additives may be added to the lead halide precursor ink, including, for example, a combination of formamidinium chloride and 5-aminovaleric acid salt.
[0188] Depending on the desired properties of the resulting perovskite material, additives (including formamidinium chloride and / or 5-aminovalerate) can be added to the lead halide precursor ink at various concentrations. In one embodiment, the additive can be added at a concentration of about 1 nM to about 1 M. In another embodiment, the additive can be added at a concentration of about 1 μM to about 1 M. In yet another embodiment, the additive can be added at a concentration of about 1 μM to about 1 mM.
[0189] In some embodiments, a Group 1 metal halide solution is formed for addition to the lead halide precursor ink. A quantity of the Group 1 metal halide can be collected in a clean, dry container under a controlled atmosphere. Suitable Group 1 metal halides include, but are not limited to: cesium iodide, cesium bromide, cesium chloride, cesium fluoride, rubidium iodide, rubidium bromide, rubidium chloride, rubidium fluoride, lithium iodide, lithium bromide, lithium chloride, lithium fluoride, sodium iodide, sodium bromide, sodium chloride, sodium fluoride, potassium iodide, potassium bromide, potassium chloride, and potassium fluoride. The Group 1 metal halide may comprise a single type of Group 1 metal halide, or it may comprise a mixture of Group 1 metal halides in precise proportions. In one embodiment, the Group 1 metal halide may include cesium iodide. In another embodiment, the Group 1 metal halide may include rubidium iodide. In yet another embodiment, the Group 1 metal halide may include sodium iodide. In another embodiment, the Group 1 metal halide may include potassium iodide.
[0190] Alternatively, other Group 1 metal salt precursors can be used in combination with or as a substitute for Group 1 metal halide salts to form Group 1 metal salt solutions. Suitable precursor group 1 metal salts may contain any combination of group 1 metals and the following anions: nitrate, nitrite, carboxylate, acetate, formate, oxalate, sulfate, sulfite, thiosulfate, phosphate, tetrafluoroborate, hexafluorophosphate, tetra(perfluorophenyl)borate, hydride, oxide, peroxide, hydroxide, nitride, arsenate, arsenite, perchlorate, carbonate, bicarbonate, chromate, dichromate, iodate, bromate, chlorate, chlorite, hypochlorite, hypobromate, cyanide, cyanate, isocyanate, fulminate, thiocyanate, isothiocyanate, azide, tetracarbonylcobaltate, carbamoyl dicyanomethane, dicyanonitromethane, dicyanamide, tricyanomethane, amide, and permanganate.
[0191] A solvent can then be added to the container to dissolve the Group 1 metal halide solid to form a Group 1 metal halide solution. Suitable solvents include, but are not limited to: anhydrous N-cyclohexyl-2-pyrrolidone, alkyl-2-pyrrolidone, dimethylformamide (DMF), dialkylformamide, dimethyl sulfoxide (DMSO), methanol, ethanol, propanol, butanol, tetrahydrofuran, formamide, tert-butylpyridine, pyridine, alkylpyridine, pyrrolidine, chlorobenzene, dichlorobenzene, dichloromethane, chloroform, and combinations thereof. In one embodiment, the lead solid is dissolved in anhydrous dimethyl sulfoxide (DMSO). The Group 1 metal halide solid can be dissolved at a temperature of about 20°C to about 150°C. In one embodiment, the Group 1 metal halide solid is dissolved at room temperature (i.e., about 25°C). The Group 1 metal halide solid can be dissolved for the required duration to form a solution, which can occur over a period of up to about 72 hours. The resulting solution forms a Group 1 metal halide solution. In some embodiments, the Group 1 metal halide solution may have a Group 1 metal halide concentration of about 0.001 M to about 10 M. In one embodiment, the Group 1 metal halide solution has a Group 1 metal halide concentration of about 1 M. In some embodiments, the Group 1 metal halide solution may also contain amino acids (e.g., 5-aminovaleric acid, histidine, glycine, lysine), amino acid hydrohalides (e.g., hydrochloride of 5-aminovaleric acid), IFL surface modifiers (SAM) (e.g., those discussed above in this specification), or combinations thereof.
[0192] Next, the lead halide solution and the Group 1 metal halide solution are mixed to form a film precursor ink. The lead halide solution and the Group 1 metal halide solution can be mixed in a certain proportion such that the resulting film precursor ink has a Group 1 metal halide molar concentration of 0% to 25% lead halide molar concentration. In a specific embodiment, the film precursor ink has a Group 1 metal halide molar concentration of 1% lead halide. In a specific embodiment, the film precursor ink has a Group 1 metal halide molar concentration of 5% lead halide. In a specific embodiment, the film precursor ink has a Group 10 metal halide molar concentration of 10% lead halide. In a specific embodiment, the film precursor ink has a Group 15 metal halide molar concentration of 15% lead halide. In a specific embodiment, the film precursor ink has a Group 10 metal halide molar concentration of 20% lead halide. In a specific embodiment, the film precursor ink has a Group 15 metal halide molar concentration of 25% lead halide. In some implementations, the lead halide solution and the Group 1 metal halide solution may be stirred or agitated during or after mixing.
[0193] Optionally, in some embodiments, water may be added to the lead halide precursor ink. In some embodiments, the solvent may also comprise 2-methoxyethanol and acetonitrile. In some embodiments, 2-methoxyethanol and acetonitrile may be added in a volume ratio of about 25:75 to about 75:25 or at least 25:75. In some embodiments, the solvent may comprise a ratio of about 1:100 to about 1:1 or about 1:100 to about 1:5 of 2-methoxyethanol and acetonitrile with DMF, based on volume. In some embodiments, the solvent may comprise at least a ratio of about 1:100 of 2-methoxyethanol and acetonitrile with DMF, based on volume. As an explanation, and without limiting the invention to any particular theory or mechanism, the presence of water can affect the growth of perovskite thin film crystals. Under normal conditions, water may be absorbed from the air in the form of vapor. It is possible to control the crystallinity of perovskite PV by adding water directly to a specific concentration of lead halide precursor ink. Suitable water includes distilled water, deionized water, or any other water source that is substantially free of contaminants, including minerals. Based on optical IV scanning, it has been found that the photoelectric conversion efficiency of perovskite PV devices with added water can be nearly three times that of completely dry devices.
[0194] Depending on the desired properties of the resulting perovskite material, water can be added to the lead halide precursor ink at various concentrations. In one embodiment, water can be added at a concentration of about 1 nL / mL to about 1 mL / mL. In another embodiment, water can be added at a concentration of about 1 μL / mL to about 0.1 mL / mL. In yet another embodiment, water can be added at a concentration of about 1 μL / mL to about 20 μL / mL.
[0195] Lead halide precursor inks or film precursor inks can then be deposited on a desired substrate. Suitable substrate layers may include any substrate layers identified above in this disclosure. As described above, lead halide precursor inks or film precursor inks can be deposited in a variety of ways, including but not limited to: drop coating, spin coating, doctor blade coating, slot die printing, screen printing, or inkjet printing. In some embodiments, lead halide precursor inks or film precursor inks can be spin-coated onto a substrate at a speed of about 500 rpm to about 10,000 rpm for a duration of about 5 seconds to about 600 seconds. In one embodiment, lead halide precursor inks or film precursor inks can be spin-coated onto a substrate at about 3,000 rpm for about 30 seconds. In some embodiments, multiple subsequent depositions of the precursor ink can be performed to form a film layer. Lead halide precursor inks or film precursor inks can be deposited onto a substrate in an ambient atmosphere with a humidity range of about 0% relative humidity to about 50% relative humidity. The lead halide precursor ink or film precursor ink can then be dried in a substantially anhydrous atmosphere (i.e., less than 30% relative humidity) to form a film.
[0196] Following the deposition of lead halide precursors or film precursors, the aforementioned giant organic cations (e.g., benzylammonium, phenethylammonium, ethylammonium, propylammonium, n-butylammonium; butane-1,4-diammonium; 1-pentylammonium; 1-hexylammonium; poly(vinylammonium); phenethylammonium; 3-phenyl-1-propylammonium; 4-phenyl-1-butylammonium; 1,3-dimethylbutylammonium; 3,3-dimethylbutylammonium; 1-heptylammonium; 1-octylammonium; 1-nonylammonium; 1-decylammonium; 1-eicosylammonium; or those described herein) or Figure 17-28A salt solution of any other giant cation shown is applied to a film formed by the deposition of a lead salt precursor and a second salt precursor. Giant organic salts may include halides, nitrates, nitrites, carboxylates, acetates, acetone-pyruvate, formates, oxalates, sulfates, sulfites, thiosulfates, phosphates, tetrafluoroborates, hexafluorophosphates, tetra(perfluorophenyl)borates, hydrides, oxides, peroxides, hydroxides, nitrides, arsenates, arsenites, perchlorates, carbonates, bicarbonates, chromates, dichromates, iodates, bromates, chlorates, chlorites, hypochlorites, hypobromates, cyanides, cyanates, isocyanates, fulminates, thiocyanates, isothiocyanates, azides, tetracarbonylcobaltate, carbamoyl dicyanomethane, dicyanonitromethane, dicyanamides, tricyanomethanes, amides, and / or permanganates of any of the aforementioned cations. A giant organic cation salt solution can be formed by dissolving the giant organic cation salt in a solvent, such as alcohols, anhydrous N-cyclohexyl-2-pyrrolidone, alkyl-2-pyrrolidone, dimethylformamide (DMF), dialkylformamide, dimethyl sulfoxide (DMSO), methanol, ethanol, propanol, butanol, tetrahydrofuran, formamide, tert-butylpyridine, pyridine, alkylpyridine, pyrrolidine, chlorobenzene, dichlorobenzene, dichloromethane, chloroform, and combinations thereof. In a particular embodiment, the giant organic cation salt can be dissolved in isopropanol. In some embodiments, the giant organic cation salt solution may have a giant organic cation salt concentration of 0.0001 M to 1.0 M. In other embodiments, the giant organic cation salt solution may have a giant organic cation salt concentration of 0.01 M to 0.1 M. In a particular embodiment, the giant organic cation salt solution may have a giant organic cation salt concentration of 0.02 M to 0.05 M. In a particular embodiment, the giant organic cation salt solution may have a giant organic cation salt concentration of about 0.05 M. The giant organic cation salt solution can be deposited onto the perovskite precursor film by any of the methods described herein with respect to solution deposition. These methods may include spraying, drop coating, spin coating, blade coating, slot die printing, screen printing, gravure printing, or inkjet printing. In one embodiment, the giant organic cation salt may be 1-butylammonium iodide. In another embodiment, the giant organic cation salt may be benzylammonium iodide. In yet another embodiment, the giant organic cation salt may be phenethylammonium iodide.
[0197] The film can then be thermally annealed at a temperature of about 20°C to about 300°C for a period of up to about 24 hours. In one embodiment, the film can be thermally annealed at a temperature of about 50°C for a period of about 10 minutes. The perovskite material active layer can then be completed by a conversion process in which the precursor film is immersed or rinsed with a salt solution containing a solvent or solvent mixture (e.g., DMF, isopropanol, methanol, ethanol, butanol, chloroform, chlorobenzene, dimethyl sulfoxide, water) and a salt with a concentration between 0.001M and 10M (e.g., methylammonium iodide, formamidinium iodide, guanidinium iodide, 1,2,2-triaminovinylammonium iodide, 5-aminovalerate hydroiodate). In some embodiments, the film can also be thermally tempered in the same manner as described in the first line of this paragraph.
[0198] In some embodiments, after film deposition and annealing, a second salt precursor (e.g., formamidinium iodide, formamidinium thiocyanate, or guanidinium thiocyanate) can be deposited onto the lead salt film, wherein the film temperature can be approximately equal to ambient temperature or a controlled temperature ranging from 0°C to 500°C. The second salt precursor can be deposited at ambient temperature or at an elevated temperature of approximately 25°C to 125°C. The second salt precursor can be deposited using a variety of methods known in the art, including but not limited to spin coating, blade coating, slot die printing, inkjet printing, gravure printing, screen printing, sputtering, PE-CVD, thermal evaporation, or spraying. In some embodiments, multiple subsequent depositions of the second salt solution can be performed to form a film layer. In some embodiments, the second salt precursor can be a solution containing one or more solvents. For example, the second salt precursor may comprise one or more of the following: anhydrous N-cyclohexyl-2-pyrrolidone, alkyl-2-pyrrolidone, dimethylformamide, dialkylformamide, dimethyl sulfoxide (DMSO), methanol, ethanol, propanol, butanol, tetrahydrofuran, formamide, tert-butylpyridine, pyridine, alkylpyridine, pyrrolidine, chlorobenzene, dichlorobenzene, dichloromethane, chloroform, and combinations thereof.
[0199] In some embodiments, any of the giant organic cation salts described herein may be combined with the second salt solution prior to deposition of the second salt solution. In a particular embodiment, the giant organic cation salt solution may be prepared as described above and mixed with the second salt solution prior to deposition. For example, the giant organic cation salt solution may have a giant organic cation salt concentration of 0.0001 M to 1.0 M. In other embodiments, the giant organic cation salt solution may have a giant organic cation salt concentration of 0.01 M to 0.1 M. In a particular embodiment, the giant organic cation salt solution may have a giant organic cation salt concentration of 0.02 M to 0.05 M. In a particular embodiment, the giant organic cation salt solution may have a giant organic cation salt concentration of about 0.05 M. In other embodiments, the giant organic cation salt solution may be deposited onto a lead halide film formed after deposition of a lead halide precursor ink or a film precursor ink. In another embodiment, the giant organic cation salt solution may be deposited onto a perovskite precursor film after deposition of the second salt solution.
[0200] Finally, the substrate with the perovskite precursor film can be annealed. Annealing the substrate can transform the lead salt precursor and the second salt precursor into a perovskite material (e.g., FAPbI3, GAPb(SCN)3, FASnI3) with a surface passivation layer of giant organic cations. Annealing can be carried out in various atmospheres at ambient pressure (e.g., about one atmosphere (760 Torr), depending on altitude and atmospheric conditions) or at pressures less than atmospheric or ambient (e.g., 1 mTorr to 500 mTorr). Annealing atmospheres can include ambient air, controlled humidity environments (e.g., 0–100 g H2O / m³), and other conditions. 3 The controlled humidity environment may consist of pure argon, pure nitrogen, pure oxygen, pure hydrogen, pure helium, pure neon, pure krypton, pure CO2, or any combination thereof. The controlled humidity environment may include an environment where the absolute humidity or % relative humidity is maintained at a fixed value, or an environment where the absolute humidity or % relative humidity varies according to a predetermined set point or a predetermined function. In a particular embodiment, annealing may occur in a controlled humidity environment with a relative humidity % greater than or equal to 0% and less than or equal to 50%. In other embodiments, annealing may occur in an environment containing greater than or equal to 0 g H2O / m³. 3 Gases and less than or equal to 20g H2O / m 3 The annealing occurs in a controlled humidity environment of the gas. In some embodiments, the annealing can occur at a temperature greater than or equal to 50°C and less than or equal to 300°C.
[0201] For example, in a specific embodiment, FAPbI3 perovskite material can be formed by the following method. First, a lead(II) halide precursor comprising a molar ratio of PbI2 to PbCl2 dissolved in anhydrous DMF of approximately 90:10 can be deposited onto a substrate by spin coating, doctor blade coating, or slot die printing. The lead(II) halide precursor ink can be applied in a substantially anhydrous atmosphere (i.e., less than 30% relative humidity or 17 g H2O / m³). 3 The film is dried in an atmosphere for approximately 1 hour (±15 minutes) to form a thin film. The film can then be thermally annealed at approximately 50°C (±10°C) for approximately 10 minutes. In other embodiments, the lead halide precursor can be deposited by inkjet printing, gravure printing, screen printing, doctor blade coating, sputtering, PE-CVD, atomic layer deposition, thermal evaporation, or spraying. Next, a 0.05 M 1-butylammonium salt solution in isopropanol can be deposited on the lead halide film. Then, a formamidinium iodide precursor comprising 15-100 mg / mL of formamidinium iodide dissolved in anhydrous isopropanol can be deposited on the lead halide film by spin coating or doctor blade coating. In other embodiments, the formamidinium iodide precursor can be deposited by inkjet printing, gravure printing, screen printing, slot die printing, sputtering, PE-CVD, atomic layer deposition, thermal evaporation, or spraying. Next, it can be deposited at approximately 25% relative humidity (approximately 4 to 7 g H₂O / m³). 3 The substrate is annealed at approximately 100°C to 200°C to form a formamidinium lead iodide (FAPbI3) perovskite material having a 1-butylammonium surface layer. In an alternative embodiment, a 1-butylammonium salt solution can be deposited onto a film formed after the deposition of a formamidinium iodide precursor. In another embodiment, the 1-butylammonium salt solution can be combined with the lead halide precursor ink before the deposition of the lead halide precursor ink. In yet another embodiment, the 1-butylammonium salt solution can be combined with the formamidinium iodide precursor before the deposition of the formamidinium iodide precursor. In yet another embodiment, the 1-butylammonium salt solution can be deposited onto the film after the deposition of the formamidinium iodide precursor and before the annealing of the film and the substrate. In yet another embodiment, the 1-butylammonium salt solution can be deposited onto the film after the annealing of the film and the substrate.
[0202] In other embodiments, using the above method and utilizing lead(II) iodide solution, cesium iodide solution, methylammonium iodide (MA) salt solution, and 1-butylammonium salt solution, a product with the formula Cs can be generated. i MA 1-i A perovskite material of PbI3, where i equals a number between 0 and 1, and has a 1-butylammonium surface layer. As another example, a perovskite material with the formula Rb can be produced using lead(II) iodide solution, rubidium iodide solution, formamidinium iodide (FA) salt solution, and 1-butylammonium salt solution. i FA1-i A perovskite material of PbI3, where i equals a number between 0 and 1, and has a surface layer of 1-butylammonium. As another example, using the above method and utilizing lead(II) iodide solution, cesium iodide solution, formamidinium iodide (FA) salt solution, and 1-butylammonium salt solution, a material with the formula Cs can be produced. i FA 1-i A perovskite material of PbI3, where i equals a number between 0 and 1, and has a surface layer of 1-butylammonium. As another example, a perovskite material with the formula K can be produced using lead(II) iodide solution, potassium iodide solution, formamidinium iodide (FA) salt solution, and 1-butylammonium salt solution. i FA 1-i A perovskite material of PbI3, where i equals a number between 0 and 1, and has a surface layer of 1-butylammonium. As another example, a perovskite material with the formula Na can be produced using lead(II) iodide solution, sodium iodide solution, formamidinium iodide (FA) salt solution, and 1-butylammonium salt solution. i FA 1-i PbI3 perovskite material, where i equals a number between 0 and 1, and has a surface layer of 1-butylammonium. As another example, a solution of lead(II) iodide-lead(II) chloride mixture, cesium iodide solution, formamidinium iodide (FA) salt solution, and 1-butylammonium salt solution can produce a material with the formula Cs. i FA 1-i PbI 3-y Cl y The perovskite material, where i equals a number between 0 and 1, y represents a number between 0 and 3, and has a surface layer with a 1-butylammonium layer.
[0203] In another embodiment, the FAPbI3 perovskite material can be formed by the following method. First, a lead(II) halide precursor ink containing a molar ratio of PbI2 to PbCl2 dissolved in anhydrous DMF of approximately 90:10 can be deposited onto a substrate by spin coating, doctor blade coating, or slot die printing. The lead(II) halide precursor ink can be deposited in a substantially anhydrous atmosphere (i.e., less than 30% relative humidity or 17 g H2O / m³). 3The lead halide precursor is dried in an atmosphere for approximately 1 hour (±15 minutes) to form a thin film. The film can then be thermally annealed at approximately 50°C (±10°C) for approximately 10 minutes. In other embodiments, the lead halide precursor can be deposited by inkjet printing, gravure printing, screen printing, sputtering, PE-CVD, atomic layer deposition, thermal evaporation, or spraying. Next, a formamidinium iodide precursor comprising a concentration of 15-60 mg / mL of formamidinium iodide dissolved in anhydrous isopropanol can be deposited on the lead halide film by spin coating or doctor blade coating. In other embodiments, the formamidinium iodide precursor can be deposited by inkjet printing, gravure printing, screen printing, slot die printing, sputtering, PE-CVD, atomic layer deposition, doctor blade coating, thermal evaporation, or spraying. After depositing lead halide precursors and formamidinium iodide precursors, a 0.04 M benzyl ammonium salt solution in isopropanol can be deposited onto the perovskite precursor film. Next, at approximately 25% relative humidity (approximately 4 to 7 g H₂O / m³), [the film can be deposited onto the perovskite precursor film]. 3 The substrate is annealed at approximately 100°C to 200°C (using a gas) to form a formammonium lead iodide (FAPbI3) perovskite material with a benzyl ammonium surface layer. In a particular embodiment, the benzyl ammonium salt solution can be deposited onto a lead halide film prior to the deposition of a formammonium iodide precursor. In another embodiment, the benzyl ammonium salt solution can be combined with the lead halide precursor ink prior to the deposition of the lead halide precursor ink. In yet another embodiment, the benzyl ammonium salt solution can be combined with the formammonium iodide precursor prior to the deposition of the formammonium iodide precursor. In some embodiments, the resulting perovskite material may have a cubic crystal structure in the bulk material away from the surface. The presence of giant organic cations near the surface of the perovskite material can lead to a non-cubic crystal structure near the surface of the perovskite material.
[0204] In other embodiments, using the above method and utilizing lead(II) iodide solution, cesium iodide solution, methylammonium iodide (MA) salt solution, and 1-butylammonium salt solution, a product with the formula Cs can be generated. i MA 1-i A perovskite material of PbI3, where i equals a number between 0 and 1, and has a benzylammonium surface layer. As another example, using the above method and utilizing lead(II) iodide solution, rubidium iodide solution, formamidinium iodide (FA) salt solution, and benzylammonium salt solution, a material with the formula Rb can be produced. i FA 1-i A perovskite material of PbI3, where i equals a number between 0 and 1, and has a surface layer of benzylammonium. As another example, using the above method and utilizing lead(II) iodide solution, cesium iodide solution, formamidinium iodide (FA) salt solution, and benzylammonium salt solution, a material with the formula Cs can be produced. i FA 1-iA perovskite material of PbI3, where i equals a number between 0 and 1, and has a surface layer of benzylammonium. As another example, using the above method and utilizing lead(II) iodide solution, potassium iodide solution, formamidinium iodide (FA) salt solution, and benzylammonium salt solution, a material with formula K can be produced. i FA 1-i A perovskite material of PbI3, where i equals a number between 0 and 1, and has a surface layer of benzylammonium. As another example, using the above method and utilizing lead(II) iodide solution, sodium iodide solution, formamidinium iodide (FA) salt solution, and benzylammonium salt solution, a material with the formula Na... i FA 1-i PbI3 perovskite material, where i equals a number between 0 and 1, and has a benzylammonium surface layer. As another example, using the above method and utilizing a lead(II)-lead(II) chloride mixture solution, a cesium iodide solution, a formamidinium iodide (FA) salt solution, and a benzylammonium salt solution, a material with the formula Cs can be produced. i FA 1-i PbI 3-y Cl y The perovskite material, where i equals a number between 0 and 1, y represents a number between 0 and 3, and has a surface layer with a benzyl ammonium layer.
[0205] The following describes a method for preparing perovskite materials using benzylammonium. First, a lead iodide precursor ink is prepared by dissolving PbI₂, PbCl₂, and cesium iodide (CsI) in a mixture of DMF and DMSO solvents. To prepare the lead iodide precursor, a 1.5 M CsI / DMSO solution is prepared by dissolving CsI in DMSO. In a specific embodiment, the CsI / DMSO solution can be prepared by stirring CsI into DMSO at a ratio of 1.5 mmol CsI / 1.0 mL anhydrous DMSO for 1 to 2.5 hours at room temperature. Next, the above CsI solution is added to a solution of PbI₂, PbCl₂, and anhydrous DMF solvent to form a 1.28 MPb solution. 2+ A solution in which the ratio of Cs to Pb is 1:10 and the ratio of I to Cl is 9:1. In a particular embodiment, 1.28 M Pb can be prepared by adding a CsI solution to a container. 2+ The solution, in this container, contains 1.26 mmol PbI₂, 0.14 mmol PbCl₂, and 1.0 mL anhydrous DMF solvent per 93.8 μL of CsI solution. Pb 2+ The solution is mixed at a temperature of 50°C to 100°C for 1.5 to 2.5 hours, and then cooled to form a lead iodide precursor ink. In a particular embodiment, Pb can be stirred at 85°C. 2+The solution is cooled for two hours by stirring at room temperature for one hour. In some embodiments, the lead iodide precursor ink may be filtered before deposition. In a specific embodiment, a 0.2 μm filter may be used to filter the lead iodide precursor ink.
[0206] Formamidinium iodide (FAI) and benzylammonium iodide (BzAI) solutions were prepared by dissolving the FAI and BzAI salts in anhydrous isopropanol (IPA) to form 0.2 M FAI and 0.05 M BzAI solutions, respectively. In a specific embodiment, both the FAI and BzAI solutions were maintained at 75°C during the subsequent coating process.
[0207] Next, lead iodide precursor ink is deposited on the substrate and then annealed to form a lead iodide film. In a particular embodiment, lead iodide precursor ink maintained at 45°C can be doctor-coated onto a substrate coated with a nickel oxide (NiO) thin film layer, and then annealed at 50°C for 10 minutes to form a lead iodide film.
[0208] Next, to form the perovskite material layer, the lead iodide film is first washed with a layer of BzAI solution, followed by the application of three layers of FAI solution. After each layer of BzAI and FAI solution is deposited, the coatings are allowed to dry before the next layer is deposited. In a particular embodiment, the BzAI and FAI solutions may be maintained at 45°C during the deposition of each coating. After the third FAI coating is deposited, the substrate and coatings may be annealed to form the perovskite material layer. In a particular embodiment, immediately after the third FAI deposition, the substrate is heated to 157°C for 5 minutes to anneal the perovskite material layer.
[0209] The above method has several advantages. For example, depositing a BzAI solution onto a lead iodide film prior to the deposition of a FAI solution can provide an intermediate template for the growth of a 3D FAPbI3 perovskite material by forming a 2D perovskite material. BzAI can react with the lead iodide film to form an intermediate 2D perovskite phase. Upon reaction with FAI after FAI solution deposition, BzAI in the 2D phase... + Cations can be completely or partially converted by FA. + Cation substitution forms a 3D FAPbI3 framework. Furthermore, BzAI can passivate crystal defects in the 3D FAPbI3 perovskite material. Compared to FAPbI3 films formed by methods without BzAI, the FAPbI3 films formed by the above method exhibit brighter (higher) photoluminescence intensity. Figure 31 Optical (absorptivity) and photoluminescence images of a perovskite photovoltaic device 3105 prepared without the addition of BzAI and a perovskite photovoltaic device 3110 prepared using BzAI, as described herein, are shown. Figure 31 The optical image of the perovskite photovoltaic device 3110 is darker, indicating a higher light absorption rate, and the photoluminescence image of the perovskite photovoltaic device 3110 is brighter than that of the perovskite photovoltaic device 3105. Furthermore, greater power output has been observed from perovskite photovoltaic devices containing BzAl. Figure 32 Power output curve 3205 is shown corresponding to a photovoltaic device without BzAI (e.g., photovoltaic device 3105), and power output curve 3210 corresponding to a photovoltaic device with BzAI as described herein (e.g., photovoltaic device 3110). Figure 32 The power output measurement described is at 100mW / cm 2 The maximum power point was measured continuously for 180 seconds under AM1.5G illumination, with a 30-second dark measurement in between, to demonstrate steady-state performance. From Figure 32 It can be seen that, compared with not using BzAI (15.0mW / cm²), 2 770mV and 19.5mA / cm 2 Compared to photovoltaic devices manufactured using other methods, those using BzAI in the fabrication process produce a greater power per unit area (16.0 mW / cm²). 2 Higher voltage (785mV) and greater current (20.3mA / cm) 2 ). Figure 33 The current-voltage (IV) scans 3320 are shown for a perovskite photovoltaic device fabricated without BzAI (labeled as sample "5r" line) and a perovskite photovoltaic device fabricated with BzAI (labeled as sample "10r" line). From... Figure 33 It can be seen that the perovskite photovoltaic device fabricated using BzAI generates a greater current over the bias range than the perovskite photovoltaic device fabricated without BzAI. Furthermore, Figure 34 Box plots showing the open-circuit voltage (Voc), short-circuit current density (Jsc), fill factor (FF), and power conversion efficiency (PCE) of six perovskite photovoltaic devices (sample 5, r = reverse scan, f = forward scan, s = steady-state measurement) without BzAI and six perovskite photovoltaic devices (sample 10) with BzAI. Figure 35 The external quantum efficiency (EQE) of six perovskite photovoltaic devices fabricated without BzAI (Figure 3505) and six perovskite photovoltaic devices fabricated with BzAI (Figure 3510) is shown. Figure 35 Each EQE curve was integrated to estimate Jsc (unit: mA / cm). 2This indicates that perovskite devices fabricated using BzAI exhibit a higher Jsc (area under the EQE curve) than perovskite devices fabricated without BzAI. Finally, Figure 36 The admittance spectra 3605 and 3610 of perovskite photovoltaic devices prepared without BzAI are shown. Compared to the admittance spectrum 3605 of the sample device without benzylammonium, admittance spectrum 3610 shows suppressed ion migration in the sample device including benzylammonium. Excessive ion migration is known to have detrimental effects on the performance and durability of perovskite devices, indicating that the addition of benzylammonium to perovskite photovoltaic devices can improve device performance and durability.
[0210] diammonium butane cation-enhanced perovskite
[0211] Incorporating 1,4-diammonium butane or other polyammonium organic compounds as described below into the crystal structure of perovskite materials can improve the properties of the materials. In one embodiment, adding 1,4-diammonium butane to FAPbI3 perovskite as described below can provide advantageous properties to the perovskite material. In some embodiments, 1,4-diammonium butane can be incorporated into the perovskite material by replacing the giant organic cation salt in the above-described method with a 1,4-diammonium butane salt, and the addition of the 1,4-diammonium butane salt (or other organic polyammonium salts described herein) can occur at any stage of the perovskite preparation method, for which the addition of giant organic cation salts in the method is as described above. Doping the crystal structure of perovskite materials with organic cations (e.g., 1,4-diammonium butane) can cause the chemical formula of the perovskite material to deviate from the “ideal” stoichiometry of the perovskite material disclosed herein. For example, the doping with such organic cations can cause the perovskite material to have a substoichiometry or superstoichiometry relative to the formula FAPbI3. In this case, the general formula of the perovskite material can be represented as C x M y X z , where x, y and z are real numbers.
[0212] In one embodiment, a 1,4-diammonium butane salt solution may be added to the lead halide precursor ink solution prior to deposition. In some embodiments, the 1,4-diammonium butane salt may be added to the lead halide precursor ink solution at a concentration of 0.001 mol% to 50 mol%. In some embodiments, the 1,4-diammonium butane salt may be added to the lead halide precursor ink solution at a concentration of 0.1 mol% to 20 mol%. In a particular embodiment, the 1,4-diammonium butane salt may be added to the lead halide precursor ink solution at a concentration of 1 mol% to 10 mol%.
[0213] In another embodiment, 1,4-diammonium butane salt may be added to the formamidinium salt solution before contacting the formamidinium salt solution with the aforementioned lead halide precursor film. In some embodiments, 1,4-diammonium butane salt may be added to the formamidinium iodide salt solution at a concentration of 0.001 mol% to 50 mol%. In some embodiments, 1,4-diammonium butane salt may be added to the formamidinium iodide salt solution at a concentration of 0.1 mol% to 20 mol%. In a particular embodiment, 1,4-diammonium butane salt may be added to the formamidinium iodide salt solution at a concentration of 1 mol% to 10 mol%.
[0214] In other embodiments, the 1,4-diammonium butane salt precursor solution can be deposited onto a lead halide film formed after lead halide precursor ink deposition, or deposited onto a perovskite precursor film after formamidinium salt solution deposition. In some embodiments, the concentration of the 1,4-diammonium butane salt precursor solution can be from 0.001 mol% to 50 mol%. In some embodiments, the concentration of the 1,4-diammonium butane salt precursor solution can be from 0.1 mol% to 20 mol%. In a particular embodiment, the concentration of the 1,4-diammonium butane salt precursor solution can be from 1 mol% to 10 mol%.
[0215] An example method for depositing a perovskite material comprising 1,4-diammonium butane includes: depositing a lead salt precursor onto a substrate to form a lead salt film, and depositing an organic cationic salt precursor comprising a first organic cationic salt onto the lead salt film to form a perovskite precursor film. The lead salt precursor or organic cationic salt precursor may comprise a 1,4-diammonium butane salt, or a 1,4-diammonium butane salt precursor may be deposited on the lead salt film or the perovskite precursor film. Finally, the substrate and the perovskite precursor film may be annealed to form a perovskite material comprising 1,4-diammonium butane. The lead salt precursor and the organic cationic salt precursor may comprise any solution described herein for preparing perovskite films.
[0216] The length between the ammonium groups in 1,4-diammonium butane is almost identical to the length between the formamidinium cations in the formamidinium lead iodide perovskite lattice. Therefore, 1,4-diammonium butane can replace two formamidinium ions during the formation of FAPbI3 material. In an alternative embodiment, other alkyl polyammonium salts can be added to the lead halide precursor ink during the formation of the perovskite material. For example, 1,8-diammonium octane, bis(4-aminobutyl)amine, and tri(4-aminobutyl)amine can be added. Furthermore, polyammonium polycations, including 1,4-diammonium butane, can provide the same benefits as the aforementioned giant organic cations through a mechanism similar to that described above regarding giant organic cations.
[0217] Figure 13This is a stylized diagram illustrating the effect of adding 1,4-diammonium butane salt during the preparation of perovskite materials on the resulting perovskite 7000. (Example) Figure 13 As shown, the 1,4-diammonium butane cation 7020 can replace two formamidinium cations 7010 in the perovskite lattice. In FAPbI3 perovskite, the spacing between formamidinium cations is approximately... The length of the 1,4-diammonium butane cation is approximately The difference is only Therefore, the 1,4-diammonium butane cation can be substituted into the perovskite lattice without significantly altering its properties or structure. In some embodiments, the addition of the 1,4-diammonium butane cation to the perovskite material enhances its performance and stability. The 1,4-diammonium butane cation can serve as a rigid structure in the perovskite material, thereby increasing its structural and chemical durability. For example, in some embodiments, perovskite materials with the addition of the 1,4-diammonium butane cation exhibit superior dry thermal stability compared to perovskite materials without the 1,4-diammonium butane cation. Furthermore, perovskite materials with the addition of the 1,4-diammonium butane cation exhibit a blue shift in their emission spectrum. In some embodiments, the 1,4-diammonium butane cation can be added to a formamidinium salt solution at a concentration of 0 to 20 mol%. In other embodiments, the 1,4-diammonium butane cation can be added to a formamidinium salt solution at a concentration of 1 to 5 mol%. In a particular embodiment, 1,4-diammonium butane cations may be added to the formamidinium salt solution at a concentration of 5 mol%.
[0218] Experimental evidence shows that adding up to 20% 1,4-diammonium butane to perovskite materials does not significantly change the lattice parameters. Figure 14 X-ray diffraction (XRD) peaks of perovskites with 0 mol%, 5 mol%, 10 mol%, and 20 mol% 1,4-diammonium butane iodide (“DABI”) were provided. For each concentration, the main peak appeared at the same point, indicating that the lattice parameters of the perovskite material did not change significantly with the addition concentration of 1,4-diammonium butane between 0 mol% and 20 mol%. The addition of 1,4-diammonium butane produced low-intensity diffraction at 2θ (less than 13°) (using Cu-Kα radiation), indicating the presence of a small amount of 2D or layered perovskite phase.
[0219] Figure 15Images are provided of perovskite samples with 0 mol%, 1 mol%, 2.5 mol%, and 5 mol% DABI exposed to 85°C and 0% relative humidity for 7 days. The perovskite material with 0 mol% DABI showed significant color reduction after 1 day, and even more significant yellowing after 7 days. This indicates that the perovskite material with 0 mol% DABI significantly degraded after 1 day of exposure to the test conditions. The perovskite material samples with 1 mol%, 2.5 mol%, and 5 mol% DABI remained dark after 7 days, indicating that adding as little as 1 mol% DABI significantly improved the so-called "dry heat" stability of the perovskite material.
[0220] Furthermore, the addition of 1,4-diammonium butane to perovskite materials results in a slight blue shift in photoluminescence compared to perovskite materials without 1,4-diammonium butane. This blue shift is attributed to the passivation of trapped states within the perovskite material due to the addition of 1,4-diammonium butane. This blue shift indicates that the addition of 1,4-diammonium butane to perovskite materials reduces the defect density in the perovskite lattice without altering the crystal structure. For example, a blue shift of 0.014 eV has been observed in FAPbI3 perovskite materials with 20 mol% 1,4-diammonium butane compared to those without 1,4-diammonium butane, i.e., a change from 1.538 eV to 1.552 eV with 20 mol% 1,4-diammonium butane.
[0221] In other embodiments, other ammonium complexes may be added during the formation of the perovskite material. For example, Figure 16 Three ammonium compounds, 1,8-diammonium octane, bis(4-aminobutyl)-ammonium, and tris(4-aminobutyl)-ammonium, are shown. They can be added to perovskite materials in the same manner as described above with respect to the 1,4-diammonium butane cation. When introduced during perovskite material formation as described above, 1,8-diammonium octane can occupy the space of two formamidinium cations (“A-sites”) in the FAPbI3 perovskite lattice. When introduced during perovskite material formation as described above, bis(4-aminobutyl)-ammonium can occupy the space of three A-sites in the FAPbI3 perovskite lattice. When introduced during perovskite material formation as described above, tris(4-aminobutyl)-ammonium can occupy the space of four A-sites in the FAPbI3 perovskite lattice. Figure 16A -C provides the option to... Figure 16 The diagram shows the stylization of the three ammonium compounds incorporated into the FAPbI3 perovskite lattice. Figure 16A This is a stylized diagram of incorporating 1,8-diammonium octane into the 7100 lattice of FAPbI3 perovskite material. (Example) Figure 16AAs shown, 1,8-diammonium octane cation 7120 can replace two formamidinium cations 7110 in the perovskite material lattice. Figure 16B This is a stylized diagram of incorporating bis(4-aminobutyl)-ammonium into the 7200 lattice of FAPbI3 perovskite material. (Example) Figure 16B As shown, bis(4-aminobutyl)-ammonium cation 7220 can replace the three formammonium cations 7210 in the perovskite lattice. Figure 16C This is a stylized diagram of incorporating tris(4-aminobutyl)-ammonium into the 7300 lattice of FAPbI3 perovskite material. For example... Figure 16 As shown in c, tris(4-aminobutyl)-ammonium cation 7320 can replace the four formamidinium cations 7310 in the perovskite lattice. In other embodiments, alkyl diammonium complexes having carbon chains of 2 to 20 carbon atoms can be added to the perovskite material. In some embodiments, combinations of ammonium complexes can be added to the perovskite material.
[0222] Cross-linked interface layer
[0223] In some embodiments, the PV device may include one or more cross-linked interface layers. Cross-linked interface layers may be physically and chemically more robust than non-cross-linked interface layers. For example, cross-linked interface layers may be harder, tougher, denser, less permeable to liquids and / or gases, and less reactive than non-cross-linked interface layers. Furthermore, cross-linked interface layers may have different electrical properties than non-cross-linked interface layers. Cross-linked interface layers may include dielectric polymers, cross-linked polymers, cross-linked fullerenes, and composites containing fullerenes and nanoparticles. In certain embodiments, the cross-linked interface layer may be deposited between the photoactive layer and the electrode as an IFL (Independent Flange Layer), for example… Figure 1 The IFL 1030 and IFL 1050.
[0224] The cross-linked interface layer may include one or more polymers and fullerenes and fullerene derivatives.
[0225] Examples of polymers include:
[0226] Polyvinyl aromatic hydrocarbons, including ortho, para, or meta isomers and di, tri, tetra, and penta-substituted derivatives, such as: polystyrene, polyvinylnaphthalene, polyvinylphenol (e.g., poly(4-vinylphenol), polyvinylaniline, polyvinylbenzoic acid, polyvinyl haloaromatic hydrocarbons (e.g., poly(4-chlorostyrene)), polyvinylpyridine (e.g., poly(4-vinylpyridine)), polyvinylthiophene, polyvinylpyrrole, polyvinylfuran, and polyvinylpyrrolidone.
[0227] Polyaromatic hydrocarbons include polyacenaphthene, polyphenylene ether, polyphenylene sulfide, polyaniline, polyfuran, polythiophene, and polypyrrole.
[0228] Polyvinyl alkanes include polyolefins (such as polyethylene, polypropylene, polyacetylene), polyvinyl alcohol, polyvinyl acetate, polyhalogenated ethylene, polyacrylic acid, polymethyl methacrylate, polyacrylonitrile, polyvinylcyclohexane, polyethyleneamine, and polyvinylthiol.
[0229] Examples of fullerenes include: C 60 C 70 and C 84 ,as well as:
[0230] Substituted fullerenes, including: azafullerenes (C 60-n n n ), borohexane (C) 60-n B n ), nitrogen boron fullerene (C 60-(n+m) N n B m ).
[0231] Endofullerenes, including metallofullerenes (M@C 60 Where M is any transition metal), trimetasphere carbon nanomaterials (M3N@C 80 (where M is any lanthanide element or transition metal) and M2@C 80 Where M is any transition metal; and nonmetal-doped fullerenes (e.g., Ng@C) 60 Where Ng = He, Ne, Ar, Kr, Xe (inert gas) and H2@C 60 ).
[0232] Exofullerenes, including: fullerenols (e.g., C10 ... 60 (OH) n (where n = 1-60), alkyl fullerenes (e.g., C 60 R n (where n = 1-60), halofullerenes: (e.g., C 60 X n Where X = F, Cl, Br or I, and n = 1-60), hydrogenated fullerenes: (e.g., C 60 H n (where n = 1-60), methylene fullerene derivatives (e.g., Bingel derivatives, including dialkyl ester methylene fullerenes: (C 60 C(CO2R)2, where R = alkyl or aryl), diynylmethylene fullerene (C 60 C(C2R)2), fullerene dihydropyrrole (C 60CR2NCCO2R); Prato derivative: C 60 C2NR, where R = alkyl or aryl; phenyl-C 61 methyl butyrate (PCMA), phenyl-C 61 methyl butyrate (PCMB), transition metal fullerene complexes, and Fulleriod (methylene bridged annulene) (an open-ring fullerene derivative).
[0233] In one embodiment, the crosslinked interface layer may be composed of fullerenes crosslinked by one or more polymers. The crosslinked polymers may include: polystyrene, methyl [6,6]-phenyl-C61-butyrate (PCBM); poly(4-vinylphenol); [6,6]-phenyl-C61-butyrate... 61 -Butyric acid (PCBA) or other poly(3-vinylphenol), poly(2-vinylphenol), poly(3,5-dihydroxystyrene), poly(3,4-dihydroxystyrene), and poly(3,4,5-trihydroxystyrene) substituted poly(4-vinylphenol), polyvinyl aryl.
[0234] In one embodiment, the crosslinked interface layer may comprise a mixture of polystyrene and silane monomers. As described herein, the silane may include any hydrosilane, hydroxysilane, halosilane, alkylsilane, alkenylsilane, alkynylsilane, cyclosilane, aromatic silane, alkoxyalkylsilane, alkoxyalkenylsilane, alkoxyaromatic silane, haloalkylsilane, haloalkenylsilane, haloalkynylsilane, and haloaromatic silane. In other embodiments, boranes, amines, phosphines, dicarboxylic acids, disulfides, and cyclophanes and cyclophane derivatives may be used to replace silanes for crosslinking the IFL. Figure 37 The structure of the cross-linked interface layer, consisting of polystyrene and halosilylalkane, before and after cross-linking is shown. Figure 37 In the illustrated embodiment, 1,6-bis-(trichlorosilyl)hexane is used to crosslink the polystyrene polymer molecules in the interface layer. However, in other embodiments, any alkane or aromatic hydrocarbon (e.g., benzene) may be used in place of the illustrated hexane, and any halogen or alkoxy group (e.g., methoxy, ethoxy) may be used in place of the chlorine group.
[0235] In another embodiment, the crosslinked interface layer may comprise a mixture of polystyrene, silane, and methyl [6,6]-phenyl-C61-butyrate (PCBM). In other embodiments, boranes, amines, phosphines, dicarboxylic acids, disulfides, and cyclophenes and cyclophene derivatives may be used to crosslink the IFL instead of silanes. Figure 38 The structure of the cross-linked interface layer, consisting of PCBM, polystyrene, and halosilylalkane, is shown before and after cross-linking. Figure 38An alkylsilane is shown for use in a crosslinked interface layer to simultaneously immobilize PCBM molecules within the crosslinked polymer interface layer.
[0236] In one embodiment, the crosslinked interface layer may comprise a mixture of poly(4-vinylphenol) and silane monomers. In other embodiments, boranes, amines, phosphines, dicarboxylic acids, disulfides, and cyclophenes and cyclophene derivatives may be used to replace silanes for crosslinking IFL. In other embodiments, poly(3-vinylphenol), poly(2-vinylphenol), poly(3,5-dihydroxystyrene), poly(3,4-dihydroxystyrene), and poly(3,4,5-trihydroxystyrene) may replace poly(4-vinylphenol). Figure 39 The structure of the cross-linked interface layer, consisting of poly(4-vinylphenol) and halosilylalkane, before and after cross-linking is shown. Figure 39 Halogenated silyl alkane is shown for use in crosslinked interface layers for poly(4-vinylphenol) polymer molecules.
[0237] In another embodiment, the crosslinked interface layer may comprise a mixture of poly(4-vinylphenol), silane, and PCBM. In other embodiments, boranes, amines, phosphines, dicarboxylic acids, disulfides, and cyclophenes and their derivatives may be used to replace silanes for IFL crosslinking. In other embodiments, poly(3-vinylphenol), poly(2-vinylphenol), poly(3,5-dihydroxystyrene), poly(3,4-dihydroxystyrene), and poly(3,4,5-trihydroxystyrene) may replace poly(4-vinylphenol). Figure 40 The structure of the cross-linked interface layer, consisting of PCBM, poly(4-vinylphenol), and halosilylalkane, before and after cross-linking is shown. Figure 40 A halosilyl alkane is shown for crosslinking poly(4-vinylphenol) polymer molecules in an interface layer while simultaneously immobilizing PCBM molecules within the crosslinked polymer interface layer.
[0238] In another embodiment, the crosslinked interface layer may comprise polystyrene, silane, and [6,6]-phenyl-C 61 A mixture of β-butyric acid (PCBA). In other embodiments, boranes, amines, phosphines, dicarboxylic acids, disulfides, and cyclophenes and cyclophene derivatives can be used to replace silanes for crosslinking IFLs. Figure 41 The structure of the cross-linked interface layer, consisting of PCBA, polystyrene, and halosilane, before and after cross-linking is shown. Figure 41 Halogenated silyl alkane is shown for crosslinking polystyrene polymer molecules and PCBA molecules in the interface layer.
[0239] In another embodiment, the crosslinked interface layer may comprise a mixture of poly(4-vinylphenol), silane, and PCBA. In other embodiments, borane, amine, phosphine, dicarboxylic acid, disulfide bonds, and cyclophenes and cyclophene derivatives may be used to replace silanes for IFL crosslinking. In other embodiments, poly(3-vinylphenol), poly(2-vinylphenol), poly(3,5-dihydroxystyrene), poly(3,4-dihydroxystyrene), and poly(3,4,5-trihydroxystyrene) may replace poly(4-vinylphenol). Figure 42 The structure of the cross-linked interface layer, consisting of PCBA, poly(4-vinylphenol) and halosilylalkane, is shown before and after cross-linking. Figure 42 Halogenated silyl alkane is shown for crosslinking poly(4-vinylphenol) polymer molecules and PCBA molecules in the interface layer. For example... Figure 42 As shown, PCBA molecules are completely immobilized within the cross-linked polymer interface layer by bonding with the silane groups of halosilyl alkane compounds.
[0240] The following describes a method for depositing a crosslinked fullerene interface layer. First, a cyclopentadiene is converted into xylene radicals. Next, the xylene radicals are deposited together with the fullerene onto a substrate to create a crosslinked interface layer, wherein the fullerene is crosslinked via one or more xylene molecules. In some embodiments, the fullerene and xylene radicals can be deposited via chemical vapor deposition, evaporation, or plasma deposition. If deposited on a perovskite layer, the interface layer deposited by this method can form a conformal coating along the surface of the perovskite material. The fullerene and crosslinked xylene polymer can fill irregularities in the perovskite surface, thereby enhancing the contact between the interface layer and the perovskite layer.
[0241] Alternative methods for depositing cross-linked fullerene interface layers are described below. First, the fullerene is functionalized to have alkanoic groups on its surface. Next, the functionalized fullerene is deposited onto a substrate. In some embodiments, the functionalized fullerene can be deposited on a perovskite layer of a photovoltaic device. Deposition methods for functionalized fullerenes include, but are not limited to, spin coating, slot die printing, chemical vapor deposition, thermal evaporation, sputtering, atomic layer deposition, extrusion, and gravure printing. Next, the fullerene coating can be treated with a silane compound to form a cross-linked silicon-fullerene interface layer. The silane compound can include any hydrosilane, hydroxysilane, halosilane, alkylsilane, alkenylsilane, alkynylsilane, cyclosilane, aromatic silane, alkoxyalkylsilane, alkoxyalkenylsilane, alkoxyaromatic silane, haloalkylsilane, haloalkenylsilane, haloalkynylsilane, and haloaromatic silane. In other embodiments, boranes, amines, phosphines, dicarboxylic acids, disulfides, and cyclophenes and their derivatives can be used to replace silanes for IFL crosslinking. In some embodiments, the silane compound can be a halosilylalkane. In a particular embodiment, the halosilylalkane can be 1,6-bis(trichlorosilyl)hexane. This silicon-fullerene crosslinked interface layer can possess the favorable electrical properties of fullerenes, which are enhanced by the physical properties of silicone. For example, the silicon-fullerene interface layer can be waterproof and flexible while maintaining the desired electrical properties of the fullerene.
[0242] Another method for depositing a crosslinked fullerene interface layer is described below. First, a polymer is dissolved in a solvent to form a polymer solution. In some embodiments, the solvent used to dissolve the polymer may include alcohols, aryl solvents, chlorinated solvents, ketones, nitriles, alkane solvents, formamides, esters, and combinations thereof. The concentration of the polymer in the solution may be in the range of about 1 μM to about 1 M. In some embodiments, the concentration of the polymer in the solution may be in the range of about 1 mM to about 10 M. Then, a fullerene is added to the polymer solution. In some embodiments, the fullerene may be added directly to the polymer solution in solid form, or it may be first dissolved in a solvent (e.g., benzene, chlorobenzene, dichlorobenzene, toluene, chloroform) and then added to the polymer solution. In some embodiments, the concentration of the added fullerene may be in the range of about 1 μM to about 10 M. In some embodiments, the concentration of the fullerene in the solution may be in the range of about 1 mM to about 1 M. Then, a crosslinking agent is added directly to the polymer solution in liquid or solid form. In some embodiments, the crosslinking agent may be dissolved in a solvent and then added to the polymer solution. Solvents used to dissolve the crosslinking agent may include alcohols, aryl solvents, chlorinated solvents, acetone, acetonitrile, alkyl solvents, formamides, esters, and combinations thereof. In some embodiments, the crosslinking agent may be added to the polymer solution prior to the addition of the fullerene. After addition to the fullerene and polymer solution, the crosslinking agent concentration may be in the range of about 1 μM to about 10 M. In some embodiments, the crosslinking agent concentration in the solution may be in the range of about 1 mM to about 1 M. In some embodiments, the solution may be prepared in a substantially air-free environment (i.e., without oxygen or water), which avoids premature crosslinking and solidification of the crosslinked interface layer ink. In some embodiments, the crosslinking agent may be added just before the application of the crosslinked interface layer ink. The polymers described herein may include any polymers disclosed herein, and the fullerenes may include any fullerenes or fullerene derivatives disclosed herein. Alternatively, as described above, the polymer may be added to the fullerene and / or crosslinking agent solution.
[0243] The crosslinked interface layer inks of this disclosure can be deposited by means of blade coating, spin coating, slot die printing, inkjet printing, gravure printing, screen printing, sputtering, spraying, drop coating, or any other solution-based deposition technique described in this disclosure. In some embodiments, deposition can occur in an atmosphere: an ambient atmosphere, a controlled atmosphere, and / or an atmosphere substantially free of water, carbon dioxide, and oxygen. The wet layer can be dried in the environment or at elevated temperatures (e.g., 0 to 250°C). The wet or dry layer can be exposed to ultraviolet radiation to promote crosslinking. In some embodiments, the crosslinking agent may require ultraviolet radiation for crosslinking.
[0244] The cross-linked interface layer can be deposited directly on the perovskite material layer, on a layer previously deposited on the perovskite layer (e.g., fullerene, dielectric material, semiconductor material, any interface layer described herein), or on the conductive substrate of this disclosure. When the cross-linked interface layer is deposited on a conductive substrate, the perovskite material can be deposited directly on the cross-linked interface layer, or one or more additional interface layers can be deposited on the cross-linked interface layer prior to depositing the perovskite material using any of the techniques described herein.
[0245] In other embodiments, various fullerenes, polymers, and crosslinking agents can be used instead of those described above. For example, Figure 43 An example of using polyhydroxyfullerene as a fullerene is shown. Figure 44 An example of using formaldehyde as a crosslinking agent is shown. Figure 45 An example is shown using poly(4-chlorostyrene) as the polymer and sodium sulfide as the crosslinking agent.
[0246] Therefore, the present invention is well suited to achieving the aforementioned and inherent objects and advantages. The specific embodiments disclosed above are merely illustrative, as the invention can be modified and practiced in different but clearly equivalent ways by way of those skilled in the art, thanks to the teachings herein. Furthermore, it is not intended to limit oneself to the details of the construction or design shown herein, except as set forth in the following claims. It is thus apparent that the specific illustrative embodiments disclosed above can be altered or modified, and all such changes are considered to be within the scope and spirit of the invention. In particular, each numerical range disclosed herein (in the form of “from about a to about b,” or equivalently, “from about a to b,” or equivalently, “from about ab”) should be understood to refer to the power set (the set of all subsets) of the respective numerical ranges, and to denote each range encompassed within a wider numerical range. Furthermore, the terms in the claims have their simple, general meaning unless otherwise explicitly and clearly defined by the patentee.
Claims
1. A photovoltaic device, comprising: First electrode; Second electrode; An active layer containing perovskite material; and A cross-linked interface layer, wherein the cross-linked interface layer is disposed between the active layer and the first or second electrode, and the cross-linked interface layer comprises: Fullerenes or fullerene derivatives; and One or more polymers, The fullerene or fullerene derivative therein, the one or more polymers, or both of them are cross-linked by a cross-linking agent. The crosslinking agent is selected from any one of silane, borane, amine, phosphine, dicarboxylic acid, cyclophenene, cyclophenene derivatives, formaldehyde, and sodium sulfide. The one or more polymers mentioned above include polyvinyl aryl; or The one or more polymers are selected from: poly(4-vinylphenol), poly(3-vinylphenol), poly(2-vinylphenol), poly(3,5-dihydroxystyrene), poly(3,4-dihydroxystyrene), poly(3,4,5-trihydroxystyrene), poly(4-chlorostyrene), and any combination thereof; or The one or more polymers are selected from: polystyrene, polyvinylnaphthalene, polyvinylphenol, polyvinylaniline, polyvinylbenzoic acid, polyvinyl haloaromatics, polyvinylpyridine, polyvinylthiophene, polyvinylpyrrole, polyvinyl furan, polyvinylpyrrolidone, and any combination thereof; or The one or more polymers are selected from: polyolefins, polyvinyl alcohol, polyvinyl acetate, polyhalogenated vinyl groups, polyacrylic acid, polymethacrylate, polyacrylonitrile, polyvinylcyclohexane, polyethyleneamine, polyvinylthiol, and any combination thereof; or The one or more polymers are selected from: polyacenaphthene, polyphenylene ether, polyphenylene sulfide, polyaniline, polyfuran, polythiophene, polypyrrole, and any combination thereof.
2. The photovoltaic device according to claim 1, wherein the fullerene derivative is selected from: methyl [6,6]-phenyl-C61-butyrate, [6,6]-phenyl-C61-butyric acid, polyhydroxyfullerene, and any combination thereof.
3. The photovoltaic device according to claim 1, wherein the fullerene derivative is selected from: substituted fullerenes, endogenous fullerenes, exogenous fullerenes, and any combination thereof.
4. The photovoltaic device according to claim 1, wherein the crosslinking agent is formaldehyde.
5. The photovoltaic device according to claim 1, wherein the silane is a halosilylalkane.
6. The photovoltaic device according to claim 1, wherein one or more polymers comprise polyvinyl aryl.
7. The photovoltaic device according to claim 1, wherein the one or more polymers are selected from: poly(4-vinylphenol), poly(3-vinylphenol), poly(2-vinylphenol), poly(3,5-dihydroxystyrene), poly(3,4-dihydroxystyrene), poly(3,4,5-trihydroxystyrene), poly(4-chlorostyrene), and any combination thereof.
8. The photovoltaic device according to claim 1, wherein the one or more polymers are selected from: polystyrene, polyvinylnaphthalene, polyvinylphenol, polyvinylaniline, polyvinylbenzoic acid, polyvinyl haloaromatic hydrocarbons, polyvinylpyridine, polyvinylthiophene, polyvinylpyrrole, polyvinyl furan, polyvinylpyrrolidone, and any combination thereof.
9. The photovoltaic device according to claim 1, wherein the one or more polymers are selected from: polyacenaphthene, polyphenylene ether, polyphenylene sulfide, polyaniline, polyfuran, polythiophene, polypyrrole, and any combination thereof.
10. The photovoltaic device according to claim 1, wherein the one or more polymers are selected from: polyolefins, polyvinyl alcohol, polyvinyl acetate, polyhalogenated ethylene, polyacrylic acid, polymethacrylate, polyacrylonitrile, polyvinylcyclohexane, polyethyleneamine, polyvinylthiol, and any combination thereof.
11. The photovoltaic device according to claim 10, wherein the polymethacrylate is polymethyl methacrylate.
12. A method for preparing perovskite photovoltaic devices, comprising: Depositing a layer containing fullerene or fullerene derivatives, a crosslinking agent, and one or more polymers on an active layer containing perovskite material; The one or more polymers, fullerenes, or fullerene derivatives, or both, are crosslinked to form a crosslinked interface layer, wherein the crosslinked interface layer contacts the active layer. The crosslinking agent is selected from any one of silane, borane, amine, phosphine, dicarboxylic acid, cyclophenene, cyclophenene derivatives, formaldehyde, and sodium sulfide. The one or more polymers mentioned above include polyvinyl aryl; or The one or more polymers are selected from: poly(4-vinylphenol), poly(3-vinylphenol), poly(2-vinylphenol), poly(3,5-dihydroxystyrene), poly(3,4-dihydroxystyrene), poly(3,4,5-trihydroxystyrene), poly(4-chlorostyrene), and any combination thereof; or The one or more polymers are selected from: polystyrene, polyvinylnaphthalene, polyvinylphenol, polyvinylaniline, polyvinylbenzoic acid, polyvinyl haloaromatics, polyvinylpyridine, polyvinylthiophene, polyvinylpyrrole, polyvinyl furan, polyvinylpyrrolidone, and any combination thereof; or The one or more polymers are selected from: polyolefins, polyvinyl alcohol, polyvinyl acetate, polyhalogenated vinyl groups, polyacrylic acid, polymethacrylate, polyacrylonitrile, polyvinylcyclohexane, polyethyleneamine, polyvinylthiol, and any combination thereof; or The one or more polymers are selected from: polyacenaphthene, polyphenylene ether, polyphenylene sulfide, polyaniline, polyfuran, polythiophene, polypyrrole, and any combination thereof.
13. The method of claim 12, further comprising functionalizing the fullerene or fullerene derivative with an alkanol.
14. The method of claim 12, wherein the one or more polymers comprise polyvinyl aryl.
15. The method according to claim 12, wherein the one or more polymers are selected from: poly(4-vinylphenol), poly(3-vinylphenol), poly(2-vinylphenol), poly(3,5-dihydroxystyrene), poly(3,4-dihydroxystyrene), poly(3,4,5-trihydroxystyrene), poly(4-chlorostyrene), and any combination thereof.
16. The method according to claim 12, wherein the fullerene derivative is selected from: methyl [6,6]-phenyl-C61-butyrate, [6,6]-phenyl-C61-butyric acid, polyhydroxyfullerene, and any combination thereof.
17. The method of claim 12, wherein the fullerene derivative is selected from: substituted fullerenes, endogenous fullerenes, exogenous fullerenes, and any combination thereof.
18. The method of claim 12, wherein the crosslinking agent is formaldehyde.
19. The method of claim 12, wherein the silane is a halosilylalkane.
20. The method of claim 12, wherein the one or more polymers are selected from: polystyrene, polyvinylnaphthalene, polyvinylphenol, polyvinylaniline, polyvinylbenzoic acid, polyvinyl haloaromatics, polyvinylpyridine, polyvinylthiophene, polyvinylpyrrole, polyvinyl furan, polyvinylpyrrolidone, and any combination thereof.
21. The method according to claim 12, wherein the one or more polymers are selected from: polyolefins, polyvinyl alcohol, polyvinyl acetate, polyhalogenated ethylene, polyacrylic acid, polymethacrylate, polyacrylonitrile, polyvinylcyclohexane, polyethyleneamine, polyvinylthiol, and any combination thereof.
22. The method of claim 21, wherein the polymethacrylate is polymethyl methacrylate.
Citation Information
Patent Citations
Process for production of porous reticulated composite materials
CN101238166A
Organic photoelectric conversion element, method for manufacturing the same, and solar cell
JP2013026483A